Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2021)
A dataset containing 1782297811 species occurrences available in GBIF matching the query: { "and" : [ "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 1782297811 records from 30709 constituent datasets: 67 records from Plasm bearing foraminifera counts from M35/1_MSN1069. 589 records from Programme ACT : Répartition Pie bavarde 2005 - 2009 Coordonnées GPS Lambert 93. 14 records from New species and records of the genus Syllis Savigny in Lamarck, 1818 (Annelida: Syllidae) from Socotra Archipelago (Indian Ocean). 12 records from Taxonomy of widespread Neotropical species of Podisus Herrich-Schäffer (Hemiptera: Pentatomidae: Asopinae): redescription of P. distinctus (Stål, 1860) and revalidation of P. fuscescens (Dallas, 1851). 53 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 29412 records from EDP Baixo Sabor: Bat Roosts - Ecological Monitoring Program (PME) (2008-2014). 6 records from Redefinition of Nipponbathynella based on the four new species from East Asia (Crustacea: Bathynellacea: Parabathynellidae). 3 records from A new species of Ledoyerella, L. kunensis sp. nov. (Amphipoda, Senticaudata, Kamakidae) from South West Africa. 1089 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 125 records from Total foraminifera counts of multinet M21/2_MSN650. 7283 records from Colecção Entomológica IIA. 6702 records from Antarctic Amphipod Crustaceans: Ant'Phipoda Database (BIANZO). 16763 records from MZFC/Coleccion de Aves. 105 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 1190 records from Coleópteros presentes en un proceso de restauración pasiva en bosque seco tropical. 6695 records from (Table 1) Stratigraphic ranges of planktonic foraminifers in ODP Hole 144-871A. 20440 records from Inventaire de la flore de Charente-Maritime 2017. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 415 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 4853 records from Inventaire des espèces végétales du sous bois des plantations de Teck de la forêt naturelle de la Lama. 411 records from SuLaMa reptile survey I 2012. 61 records from Shrews of Poland. 1070 records from DMNS Egg Collection (Arctos). 2 records from A molecular phylogenetic hypothesis for the Asian agamid lizard genus Phrynocephalus reveals discrete biogeographic clades implicated by plate tectonics. 9 records from Nannofossil abundance of Hole 2-11. 1 records from Happywhale - Layard's beaked whale in Southern Ocean. 18 records from Bonaire Turtle Tracking 2012 (aggregated per 1-degree cell). 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 3 records from A new species of the genus Larsia Fittkau (Diptera: Chironomidae) from India with cladistic analysis and a world key to the known males. 186 records from New Staphylinidae (Coleoptera) records with new collection data from New Brunswick, Canada. I. Aleocharinae. 1870 records from Planktonic foraminiferal abundances, and sea surface and export production reconstructions of sediment core SU92-03. 100 records from Fossil occurrence of planktonic foraminifera from IODP Hole 322-C0012A. 15 records from Nannofossil abundance of Hole 6-48B. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 15 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 5229 records from European Moth Nights. 14 records from A review of Scaphisomatini from Sulawesi, with descriptions of ten new species (Coleoptera: Staphylinidae: Scaphidiinae). 9174 records from Relevés of Main Vegetation Types of the Prioksko-Terrasnyi Biosphere Reserve (2019-2020). 172 records from Données du/de la naturaliste Roquinarc'h Océane provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Abundance of microplankton from bottle APRIL-2000-K3. 231 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 600 records from Occurrence data of Birds of the Upper Tana Basin, Kenya. 6775 records from Données du naturaliste MIGUET Pierre provenant de la base de donnée du SINP Île-de-France CETTIA. 9 records from Troglocoelotes gen. n., a new genus of Coelotinae spiders (Araneae, Agelenidae) from caves in South China. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 361 records from An updated checklist of aquatic plants of Myanmar and Thailand. 15554 records from A practical introduction to microbial molecular ecology through the use of iChips. 1 records from Registro de Chromolaena tacotana asociado al proyecto: Relación estructura-actividad anti-cáncer de flavonoides sobre líneas celulares cancerosas. 1702 records from BioGIS - Bryophytes - HUJ collections. 1036 records from BUND - Dassower See (Lübeck/Dassow). 59978 records from Données naturalistes de Monsieur François FOURNIER. 957 records from Collection de longicornes et autres coléoptères saproxyliques de Lionel Valladares. 1000 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 27 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 54016 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 1 records from Gymnoamblyopus novaeguineae, a new genus and species of worm goby from Papua New Guinea (Gobiidae: Amblyopinae).. 4 records from Sächsische Schweiz (Wehlener Gebiet). 1 records from Coarazuphium lundi (Carabidae: Zuphiini), a new Brazilian troglobitic beetle with the designation of a neotype for C. pains Álvares & Ferreira, 2002. 19 records from Schizorhynchia Meixner, 1928 (Platyhelminthes, Rhabdocoela) of the Iberian Peninsula, with a description of four new species from Portugal. 748 records from Universidad del Valle de Guatemala - Colección de Artrópodos (UVGC). 29 records from Ours 2004 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 2208 records from marine sediment metagenome Raw sequence reads. 522 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 13 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1 records from Contribution to the knowledge of Mediterranean lichen-feeding darkling beetles of the genus Stenohelops Reitter, 1922 (Coleoptera: Tenebrionidae). 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 776 records from Programme ACT : Répartition Pie bavarde 2010 - 2014 Coordonnées GPS Lambert 93. 39 records from Planktic foraminifera abundance of Hole 14-137. 101 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 1 records from A new Physoschistura from a Salween affluent in western Yunnan (Teleostei: Nemacheilidae). 2531 records from University of Wyoming Museum of Vertebrates (UWYMV) Bird Collection (Arctos). 751 records from Données naturalistes de Monsieur JOURDE Rémi. 873 records from Programme ACT : Répartition Geai des chênes 2008 - 2012 Coordonnées GPS Lambert 93. 16 records from On the genus Tylorida Simon, 1894 with the first record of the genus Atelidea Simon, 1895 from India (Araneae: Tetragnathidae, Leucauginae). 9 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 4 records from A new species of the genus Urumaelmis Satô (Coleoptera, Elmidae, Macronychini) from Kyushu Island, Japan. 35 records from Occurrence of mammalia relicts at site l´Abri de Campalou. 10 records from New Brazilian Tafaliscina increase the diversity of this Neotropical cricket clade (Orthoptera: Grylloidea: Gryllidae: Oecanthinae: Paroecanthini). 1 records from A new species of Allomallodon Santos-Silva and Galileo, 2010 from Bolivia (Coleoptera: Cerambycidae: Prioninae: Macrotomini). 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 582 records from Occurrence data of Swallowtail butterflies (Lepidoptera: Papilionidae) in the Zoology Museum of Makerere University. 2 records from Four species of Tubifex Lamarck (Annelida: Oligochaeta: Naididae) from Tibet, China. 130 records from Total foraminifera counts of multinet M21/6_MSN784. 129 records from Occurrence data of mayflies available at the National Museums of Kenya's Natural History Collections, Invertebrates Zoology Section.. 48 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 66 records from Nine new species of Uramya Robineau-Desvoidy (Diptera: Tachinidae) from Area de Conservación Guanacaste in northwestern Costa Rica, with a key to their identification. 120 records from BIRDRACE The early birds. 1933 records from Données odonates collectées par le CEN Aquitaine entre 1995 et 2015. 50076 records from DFO Pacific Outside South Hard Bottom Longline Surveys. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 2 records from Catalogue of distribution of lizards (Reptilia: Squamata) from the Brazilian Amazonia. III. Anguidae, Scincidae, Teiidae. 17 records from A checklist of epibiont suctorian and peritrich ciliates (Ciliophora) on halacarid and hydrachnid mites (Acari: Halacaridae & Hydrachnidia). 92 records from Protozoa Abundance_Microbial Parameters. 31 records from Bulletin d'informations de l'Association française de Lichénologie. 38 records from Nannofossil abundance of Hole 10-89. 4 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 45 records from (Table 6) Abundances of dinoflagellates in ODP Hole 104-642B. 91 records from Nannofossil abundance of Hole 30-285A. 32 records from Antarctic Pycnogonids II. 59788 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 3 records from Demoulinia Gillies 1990 and two unnamed genera of the plesiomorphon Protopatellata (Ephemeroptera, Baetidae) from South Africa. 23648 records from WTSWW Data: All Taxa (West Wales). 1494 records from EDP Foz Tua Nocturnal Birds - Ecological Monitoring Program [2011-2017]. 2560 records from Upper Silesian Museum, Bird Observations. 2 records from Two new Thiratoscirtus species from Gabon (Araneae, Salticidae, Thiratoscirtinae). 78 records from New species and records of Caulleriella (Annelida, Cirratulidae) from shelf and slope depths of the Western North Atlantic Ocean. 147 records from The genusParascepsis Dognin, 1923 (Lepidoptera, Erebidae, Arctiinae, Ctenuchina) in Peru, with the description of three new species, a new combination and their geographical distributions. 9 records from (Table 3) Relative percent abundance of planktic Foraminifera at DSDP Site 10-95, Paleocene. 758 records from (Appendix Table 2) Raw counts of planktonic foraminiferal species from sediment core MD01-2390. 135 records from Range table from benthic foraminifers in ODP Hole 171-1050A. 1 records from Occurrence of mammalia relicts at site Stockton-on-Tees. 11 records from Twenty more new species of Agrilus (Coleoptera: Buprestidae: Agrilinae) from the Oriental region. 269 records from SEWBReC Springtails and allies (South East Wales). 1 records from New Lepidocyrtus Bourlet, 1839 from riverine woodland in Hungary (Collembola, Entomobryidae). 62 records from Polychaeta and Oligochaeta of the Auckland and Campbell Islands, New Zealand, 1941-1945. 102 records from Benthic foraminifera abundance in ODP Leg 155 holes. 16 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 69 records from Unter hellen Zinnen und finsteren Grotten. 354 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 75 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 91 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 13868 records from Données faune Nature 18 - 2017. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 53 records from Données du/de la naturaliste Dubois Yves provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from Bryozoans Specimens of Akita Prefectural Museum. 76 records from Plasm bearing foraminifera counts from multinet SO119_MSN1295. 18 records from Anfibios presentes en el Cerro Jánano. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 120 records from Données espèces - Expertise IPE 79. 1715184 records from NBIS Records to December 2016. 25 records from Planktic foraminifera abundance of Hole 51-417B. 1426 records from SPC PROCFish/C Invertebrates Observations Kiribati 2004. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 2590 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 931 records from South American Antarctic Marine Biodiversity Literature. 189 records from Chas.H. O'Donoghue, D.Sc. & Dora de Watteville,M.A. The fishery grounds near Alexandria. XX-Bryozoa. Notes and Memoirs No 34. Hydrobiology and Fisheries Directorate, Egypt.. 14497 records from A grid database on vascular plant distribution in the Meshchersky National Park, Ryazan Oblast, Russia. 81 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 5 records from Revisiting the Andean butterfly Eryphanis zolvizora group (Lepidoptera, Nymphalidae): one or several species?. 638 records from Range table from planktonic foraminifers in ODP Hole 144-873B. 50 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 286 records from California State University, Long Beach Birds. 1930 records from Données de la naturaliste Lemoine Delphine provenant de la base de donnée du SINP Île-de-France CETTIA. 17 records from Thirteen new records of ferns from Brazil. 713 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 384 records from Marine metagenome ICM_AWP. 558 records from SOCAL FZN4 Marine Mammal Aerial Monitoring 2013. 3588 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 121 records from Foraminifera abundance of sediment core IN68-28. 4 records from Delimitation and description of three new species of Himalopsyche (Trichoptera: Rhyacophilidae) from the Hengduan Mountains, China. 3 records from Hurleyella, a new genus of Nearctic Dolichopodidae (Diptera). 26 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 1814 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 98 records from Données opportunistes sur les odonates. 350 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 14980 records from Données Entomologiques A. HORELLOU 1988-2018. 285 records from Données du/de la naturaliste Cousin Richard provenant de la base de donnée du SINP Île-de-France CETTIA. 321 records from Foraminifera abundance of Hole 74-526A. 48 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 1516 records from Records of Halicarcinus planatus at sub-Antarctic regions. 1 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 600 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 2 records from Taxonomy of the Cixiidae (Hemiptera, Fulgoromorpha) from the Madeira archipelago. 1110 records from (Table 2) The presence and absence of whole and/or fragmented planktonic and benthic foraminifers at DSDP Hole 93-603. 232 records from Planktic foraminifera abundance of Hole 21-207. 8 records from (Tab. 9) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 17-166, Magellan Ridge, southwest of Hawaii. 24 records from Sarcodine counts and carbon biomass at station TT012_5-TM9. 11321 records from WOLL AVH data. 203 records from Insectos de la expedición al municipio de San Francisco, Cundinamarca - Caracterizaciones Humboldt. 84 records from Ostracoda abundance of Hole 48-403. 19 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 34 records from New species and new records of Mydidae from the Afrotropical and Oriental regions (Insecta, Diptera, Asiloidea). 572 records from New Mexico Museum of Natural History and Science (NMMNH&S) Herbarium specimens (Arctos). 2714 records from Données de la Réserve Naturelle Nationale de Saint-Quentin-en-Yvelines provenant de la base de donnée du SINP Île-de-France CETTIA. 94 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 20 records from Microzooplankton abundance and biomass at station NBP97-08-05-1. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 2497 records from Données des collections d'algues du MNHN. 2344 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 499 records from Range table from benthic foraminifers in ODP Hole 146-889A. 98 records from Warnowtal (Rostock). 71 records from Invasive plants in Luronium natans habitats in Flanders, Belgium. 1897 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 371 records from Bannwald Burghauser Forst. 948 records from Bulletin du Muséum d'Histoire Naturelle [1895- ]. 18 records from Sarcodine counts and carbon biomass at station TT007_8-CTD99. 290 records from Données 2016 Pélobate brun Comité Départemental de Protection de la Nature et de l'Environnement. 26 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 2 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 54 records from Three new goatfishes of the genus Upeneus (Mullidae) from the Indo-Pacific, with a redescription of colour patterns in U. margarethae. 20 records from Revision of the genus Parvimysis (Mysida, Mysidae) with descriptions of five new species from coastal waters of the Caribbean. 13 records from The genus Mecodema Blanchard 1853 (Coleoptera: Carabidae: Broscini) from the North Island, New Zealand. 386063 records from Compost microbe establishment and growth in agricultural soils. 20 records from Bostryx tortoranus (Doering, 1879) species complex (Gastropoda: Stylommatophora: Bulimulidae), a review of taxonomy and distribution of endemic species from Argentina. 202122 records from National Benthic Inventory. 107 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 10 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 2127 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 16 records from Phenological Center - Fishes (Murmansk). 358 records from Comunidad fitoplanctónica presente en la Bahía de Buenaventura 2018. 63 records from Occurrence of mammalia relicts at site Laugerie-Haut e-Est. 756 records from Benthic foraminifera and algae abundance of Hole 81-552A. 19 records from Chronicle of Nature - Phenology of Insects of National Park Bashkirija. 20520 records from University of Guam Insect Collection. 111 records from Abundance and biomass of phytoplankton in Butakova Bay, Aral Sea, in september 1990. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 298 records from Planktic foraminifera abundance of Hole 32-310. 19 records from Dinoflagellate abundance of Hole 81-554. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 3 records from Two new species in the genus Indolipa Emeljanov, 2001 (Hemiptera: Fulgoromorpha: Cixiidae: Pentastirini) from China. 2 records from First records of the jewel beetles Chrysobothris desmaresti (Laporte & Gory, 1836) and Hiperantha stempelmanni Berg, 1889 (Coleoptera: Buprestidae) in Bolivia. 4 records from Taxonomy of ant species (Hymenoptera: Formicidae) collected by pitfall traps from Sinai and Delta region, Egypt.. 351600 records from Finnish Floristic Database (Vascular plant data of Kevo Subarctic Research Institute). 1 records from A Scanning Electron Microscopy Study Of The Epiprocts Of Western North American Sweltsa (Plecoptera: Chloroperlidae). 158 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 102 records from Nannofossil abundance of Hole 24-232. 39 records from Macrofauna biomass in surface sediment sampled during cruise DI231. 167 records from AMAPPS Southeast Aerial Cruise Fall 2016. 3 records from Holomorphology of Kamimuria peppapiggia sp. n. (Plecoptera: Perlidae) from the foothills of Taihang Mountains, Henan Province of China. 655 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 1 records from A new species of Synopeas (Hymenoptera: Platygastridae) parasitizing Pauropsylla cf. depressa (Psylloidea: Triozidae) in India. 1 records from Three new species of the free-living marine nematode Metoncholaimus Filipjev 1918 (Enoplida, Oncholaimidae) from Argentinean coasts. 178 records from Benthic foraminifera and algae abundance of Hole 81-554. 1 records from Dressed in black. A New Ansonia Stoliczka, 1870 (Lissamphibia: Anura: Bufonidae) from Gunung Murud, Sarawak, East Malaysia (Borneo). 1189 records from UWIZM Molluscs. 26 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/041-2. 4083 records from MCP-Aves - Coleção de Aves. 135 records from Nannofossil abundance of Hole 36-329. 243726 records from Carnet B Lorraine. 27 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 100 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 143 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 778 records from Bird specimens of Saitama Museum of Natural History. 371 records from orthopteracollections-nhmj-ioj. 1 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 2 records from Description and phylogenetic relationships of a new trans-Andean species of Elachistocleis Parker 1927 (Amphibia, Anura, Microhylidae). 10788 records from Collections of Bioclass, school #179, Moscow. 360958 records from Seasearch Marine Surveys in England. 336 records from Aves del cerro Tapartó, Santa Cecilia - Risaralda. 2020. 27 records from Planktic foraminifera abundance of Hole 84-566C. 9 records from A review of the genus Coccoglypta Pilsbry, 1895 (Gastropoda: Pulmonata: Camaenidae). 54550 records from Digital Aerial Baseline Survey of Marine Wildlife in Support of Offshore Wind Energy - OPA 2016. 17 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 3 records from Porphyrocrinus daniellalevyae n. sp. (Echinodermata: Crinoidea), a sea lily from the tropical western Atlantic with a unique crown pattern. 988 records from flower availability 2008 Alb-korrigiert. 14576 records from Inventario de flora, avifauna, mamíferos, mariposas y peces realizado en el sector de Puerto Abeja y durante la expedición científica en la ventana Mesay en el sector sur del Parque Nacional Natural Serranía de Chiribiquete. 4 records from Dinoflagellate abundance of Hole 14-144. 6 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 34 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 274611 records from Digitalización y sistematización de las colecciones biológicas del INECOL (Herbario). 35 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2015. 3 records from A new species of Rhabdops Boulenger, 1893 (Serpentes: Natricinae) from the northern Western Ghats region of India. 147 records from Range table from benthic foraminifers in ODP Hole 161-974B. 2963 records from Collection Trichoptera - SMF. 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 16 records from Seven new species of the Stenus cirrus group (Coleoptera, Staphylinidae) from Guangxi, South China. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 7 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 41 records from Swedish Malaise Trap Project (SMTP) - Sphecidae (s lat). 3740 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Olekminsky. 99 records from Planktic foraminifera abundance of Hole 27-262. 1910 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 27 records from Planktic foraminifera abundance of Hole 27-260. 137028 records from Arizona State University Hasbrouck Insect Collection. 62 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 84 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 3361 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Herpetológica Chetumal). 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 1156 records from Legume Collections of the Plant Genetic Resources Research Institute (CSIR-PGRRI),Ghana. 35 records from The Xiphydria annulitibia group in northeastern Asia (Hymenoptera, Xiphydriidae). 1480 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 1120 records from Range table from planktonic foraminifers in ODP Hole 152-919A. 748 records from AMAPPS Northeast Aerial Cruise Summer 2010. 18 records from Naturtag. 16071 records from Herbier Louis-Marie (QFA) - Collection de lichens. 457 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 3 records from Happywhale - Adelie Penguin in Southern Ocean. 41 records from HRC CRC Small Vessel-Based Monitoring Surveys July 2006. 87901 records from MDFRC macroinvertebrate survey. 128 records from Inventaire des reptiles 2014. 76 records from A synopsis of Phyllogomphoides Belle, 1970 (Odonata: Gomphidae) of Mexico: taxonomy and distribution. 422108 records from NOAA AFSC North Pacific Groundfish Observer. 3272 records from Mammifères marins Guadeloupe Antilles françaises (AET). Suppléments. 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 3 records from New erythroneurine leafhopper species from the Australian realm (Hemiptera: Cicadellidae: Typhlocybinae). 64 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 16 records from Hazel Dormouse in Ireland. 100 records from Range table from planktonic foraminifers in ODP Hole 171-1053A. 30 records from New taxa of Tateidae (Caenogastropoda, Truncatelloidea) from springs associated with the Great Artesian Basin and Einasleigh Uplands, Queensland, with the description of two related taxa from eastern coastal drainages. 1027 records from Programme ACT : Répartition Merle noir 1996 - 2000 Coordonnées GPS Lambert 93. 7 records from A checklist of the Ukrainian Xoridinae (Hymenoptera, Ichneumonidae). 115 records from Total foraminifera counts of multinet M21/4_MSN694. 8 records from Review of the genus Valdasus Stål, 1860 (Heteroptera, Miridae, Cylapinae), with descriptions of four new species from Brazil, Ecuador and French Guiana. 46 records from An der Ohm, (Wettsaasen). 48 records from Phytoplankton abundance at station Rigel_4_2005-08 in August 2005, Chipana, Chile. 568 records from Philippine Mollusk Symbiont - ICBG Collection. 185 records from Inventaire des odonates d'intérêt communautaire. 3 records from Manx Basking Shark Watch 2017-2018 (aggregated per 1-degree cell). 149 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 13 records from Review of the genus Lesteva Latreille, 1797 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini) of Iran and adjacent territories. 1893 records from Données de la collection de Hubert Piguet - Famille des Elateridae. 2419 records from Flora de las sabanas inundables de las cuencas de los ríos Bita, Manacacías y Cravo Sur - SULU II. 10 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 101 records from Radiolaria assemblage in sediment core GIK23400-3. 526 records from Range table from benthic foraminifers in ODP Hole 151-913B. 198 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 259 records from Programme ACT : Répartition Alouette lulu 2009 - 2013 Coordonnées GPS Lambert 93. 124 records from Kirkliston Range stream monitoring. 31115 records from 16S rDNA amplicon of Bacteria and Archaea Metagenome. 1088 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 115 records from Israel Sea Turtle Tracking Project 2008: Loggerhead & Green Turtles (aggregated per 1-degree cell). 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 3 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 16838 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 31 records from HRC SCC Vessel-Based Monitoring Surveys February 2010. 3 records from ALLIUM (AMARYLLIDACEAE) SPECIES IN PAKISTAN: TWO NEW RECORDS AND A NEW SPECIES FROM ZHOB (BALOCHISTAN). 75 records from Happywhale - Bryde's whale in South Atlantic Ocean. 2763 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 5 records from Minute but constant morphological differences within members of Stenothoidae: the Stenothoe gallensis group with four new members, keys to Stenothoe worldwide, a new species of Parametopa and Sudanea n. gen. (Crustacea: Amphipoda). 1 records from A new species of Limnonectes (Amphibia: Anura: Dicroglossidae) from Vietnam. 94 records from Distribution of planktonic foraminifera of sediment core SH1972_3. 121 records from Registros de dípteros asociados al proyecto: Estratificación espacial del dengue basado en la identificación de factores de riesgo en el departamento del Cauca. 5 records from A new species of Sarmydus Pascoe, 1867 (Cerambycidae: Prioninae: Anacolini) from Nicobar Island, India. 1 records from First record of the genus Chandleriella Hlaváč (Coleoptera: Staphylinidae: Pselaphinae) from China, with description of a second species. 3 records from A new species of Caenis Stephens, 1835 (Ephemeroptera: Caenidae) from Tamil Nadu, Southern India. 454 records from British Reptiles & Amphibians in the collections of World Museum Liverpool. 1 records from Timea bioxyasterina sp. n., a new species from the Northeastern coast of Brazil (Demospongiae, Hadromerida). 6 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 1 records from Dorcus tianlongi, a new species from central China (Coleoptera: Lucanidae: Lucaninae). 2 records from Dolichogenidea fernandeztrianai sp. nov. (Hymenoptera: Braconidae, Microgastrinae) from Iran. 95 records from Marine algal (seaweed) flora of Faial Island, Azores. 2 records from A new species of Acanthella Schmidt, 1862 (Porifera, Demospongiae, Dictyonellidae) from northeast region, Brazil. 12595 records from AMNH Invertebrate Paleontology WIS-Cretaceous Research Collection. 57 records from Taxonomy of Probolodus Eigenmann, 1911 (Characiformes: Characidae) with description of two new species, and comments about the phylogenetic relationships and biogeography of the genus. 21 records from New data on brachypterous Paederus (Coleoptera, Staphylinidae) of mainland China. 7 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 191-1179C. 3500 records from Pelagic sediment metagenome of Gulf of Kutch. 4722 records from Dataflos. 3 records from A new species of Flavoperla Chu, 1929 (Plecoptera: Perlidae) from Guangxi Zhuang Autonomous Region of southern China. 2743 records from marine sediment metagenome Raw sequence reads. 9 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 130 records from Dubai Turtle Rehabilitation Project (aggregated per 1-degree cell). 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 26 records from Occurrence of mammalia relicts at site Rusenschloß. 794 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 1211 records from Tejidos de ejemplares colectados en el Páramo de Chingaza - Proyecto Colombia Bio. 96 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 1338 records from Kallisti Limnes subsea pools Metagenome Study. 11 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 168 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 298 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 1 records from A new, peculiar genus of Cossoninae (Coleoptera, Curculionidae) from Oman with description of a new species, larva and notes on biology. 15251 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 40738 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 1 records from Diversity of methyl alkyl succinate synthase genes in hydrocarbon seep sediments (Raw sequence reads). 1 records from Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate. 13 records from Lane 6 Analysis. 3939 records from Census of plant species in Pahou forest reserve. 3 records from A new species of Capnia (Plecoptera: Capniidae) from Lesser Khingan Range (Amur River Basin, Far East of Russia). 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 6578 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new genus and species of anophthalmous Otiorhynchini from Greece, with a new synonymy and new combinations (Coleoptera: Curculionidae, Entiminae). 67 records from Relative abundance of ostracods in sediment core Sv09. 904 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 781 records from Ecological study of the plankton in the port of Ostend in 1965. 192 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 93324 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 49 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 14 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 7 records from A New Species Of Perlesta (Plecoptera: Perlidae) From North Carolina With Additional Records For North Carolina And Virginia. 296 records from HRC SCC Aerial-Based Monitoring Survey February 2010. 20442 records from Trondheim urban biodyversity survey. 94 records from Données du/de la naturaliste LUSTRAT Philippe provenant de la base de donnée du SINP Île-de-France CETTIA. 58 records from Swedish Malaise Trap Project (SMTP) - Banchini. 142 records from Size of planktic foraminifera at CTD station PS55/083-1. 303 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 36369 records from R. L. McGregor Herbarium Lichen Collection. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 12 records from A revision of the spider genus Anemesia (Araneae, Cyrtaucheniidae). 11034 records from Oregon Bee Atlas Survey Data: 2018. 200 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 557 records from Corn bunting breeding distribution in Scotland. 1210 records from NEFSC Marine Mammal Abundance Cruise 2004 Passive Acoustic Monitoring - Rainbow Click Detections. 919 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 71 records from Foraminifera species abundances from tow TT007_7-MOC13. 4 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 2 records from A new species of the genus Microhyla Tschudi, 1838 (Amphibia: Anura: Microhylidae) from Tay Nguyen Plateau, Central Vietnam. 40011 records from Banded Iron Formation and Greenstone survey data. 38 records from Microzooplankton abundance and biomass at station TT045_19-3. 41 records from Hydroptilidae (Trichoptera) of Angola, a new genus, seven new species, and five new records. 4 records from New records and checklist of Chilocorini (Coleoptera: Coccinellidae) from China. 1 records from The genus Mytilina in China, with description of a new species (Rotifera: Monogononta: Mytilinidae). 6433 records from Modernisation des ZNIEFF du PnrL. 419 records from A survey of the weevils of Ukraine (Coleoptera: Curculionoidea). 10 records from The West and Central African species of Vepris Comm. ex A. Juss. (Rutaceae) with simple or unifoliolate leaves, including two new combinations. 1 records from A review of Garra (Teleostei: Cypriniformes) from two rivers in West Yunnan, China with description of a new species. 3 records from Dombeya sevathianii (Malvaceae): A new critically endangered species endemic to Mauritius (Indian Ocean). 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 12 records from Occurrence of mammalia relicts at site Niederlehme. 1264 records from Grand Voyeux - Suivis scientifiques. 38 records from Eight new species of the genus Anaplecta Burmeister, 1838 (Blattodea: Blattoidea: Anaplectidae) from China based on molecular and morphological data. 155 records from Taxonomic revision of the genus Prionopelta Mayr, 1866 (Formicidae: Amblyoponinae) for the Neotropical region. 11 records from (Table 2) Population density and zoobenthos biomass in bottom communities of the Novosibirsk Polynya in September 2008. 86 records from UWIZM Cnidarians. 237 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/593-18. 1 records from Planothidium galaicum sp. nov. (Bacillariophyta, Achnanthidiaceae), a new diatom species from Galician coast, Spain. 69 records from BIRDRACE Pfeifenten. 299 records from Colección Taxonómica Nacional de Insectos “Luis María Murillo” (CTNI). 150 records from Ningaloo Outlook Whale Shark tracking (aggregated per 1-degree cell). 5335 records from Marine metagenome ICM_JRV. 2 records from Microzooplankton abundance and biomass at station TT050_25-4. 146 records from Données de la naturaliste Laurence Beauchamp. 164 records from Ladybirds of Ireland. 52 records from Collections ichtyologiques et herpétologiques (BOUM). 80 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 78 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 14341 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Invertebrates National Collection (MACNIn). 174667 records from Tasmanian Museum and Art Gallery provider for OZCAM. 938 records from TTRS Mammals. 6 records from Neotropical Chvalaea Papp & Földvári (Diptera: Hybotidae: Ocydromiinae): new records, an illustrated key to species and description of three new species. 18 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 6 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 686 records from Expediciones en biodiversidad alrededor del Cacao en el marco del proyecto Colombia Bio. 740 records from Monitoring data of marine turtles on the Togolese coast over 2012-2013 years. 4575 records from Narragansett Bay, RI Sediments Targeted Locus (Loci). 2 records from Benthic foraminifera abundance of Hole 42-376. 99 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 6192 records from NE Scotland fish records 1800-2010. 1615 records from NEON Biorepository Mammal Collection (Vouchers [Standard Sampling]). 19 records from Colección Ornitológica del Museo de Historia Natural de la Universidad de la Amazonia. 45 records from Brown bear monitoring data from Deosai National Park. 436 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 69 records from Matter enrichment of the macrofauna community of MAC station 13077-001. 2 records from Description of a new snake eel Ophichthus olivaceus (Teleostei: Anguilliformes Ophichthidae) from the Red Sea. 2336 records from Collembola of Prioksko-Terrasny Nature Reserve: multi-scale spatial distribution analysis in pine forests. 2 records from South American Leaf-Cutter Bees (Genus Megachile) Of The Subgenera Rhyssomegachile And Zonomegachile, With Two New Subgenera (Hymenoptera: Megachilidae). 93662 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 57913 records from Fichier communal des ongulés. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 1 records from Occurrence of mammalia relicts at site High Furlong. 36 records from University of Sindh Jamshoro Herbarium. 602 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 5 records from Revision of Tomocerus similis Chen & Ma, with discussion of the kinoshitai complex and the distal tibiotarsal chaetae in Tomocerinae (Collembola, Tomoceridae). 25 records from Small, rare and little known: new records and species of Cardiomya (Bivalvia: Cuspidariidae) from Brazil. 1254 records from Bryozoa, Brachiopoda and Entoprocta (TSZBr) UiT Tromsø Museum. 420 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 29 records from Systematics of the enigmatic South American Streblopus Van Lansberge, 1874 dung beetles and their transatlantic origin: a case study on the role of dispersal events in the biogeographical history of the Scarabaeinae (Coleoptera: Scarabaeidae). 9176 records from Réseau de surveillance Polynesia Mana - Peuplements de poissons. 115 records from Living Cirripedia. 89 records from Faunal assemblage of sediment core TR149-32. 787 records from Programme ACT : Répartition Pie bavarde 2009 - 2013 Coordonnées GPS Lambert 93. 2 records from Zur Oribatidenfauna des Leopoldsberges von Wien (1. Beitrag). 62 records from Tree-dwelling ant survey (Hymenoptera, Formicidae) in Mitaraka, French Guiana. 473 records from Benthic foraminiferal number, diversity, and species abundance of size fraction >125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 1 records from Madangella altirostris, a new genus and species of palaemonid shrimps (Crustacea: Decapoda: Palaemonidae) from Papua New Guinea. 2 records from Four new species of Magelona (Annelida: Magelonidae) from Easter Island, Guam and Hawaii. 1 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 218 records from Land and freshwater molluscs of Northern Spain. 1 records from A new species of the hermit crab genus Alainopaguroides McLaughlin, 1997 (Crustacea: Decapoda: Anomura: Paguridae) from the South China Sea. 3775 records from Données naturalistes de Charlotte PICARD. 4 records from Ostracoda abundance of Hole 44-390. 2 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 98 records from Plasm bearing foraminifera counts of multinet M21/1_MSN615. 131 records from Manejo campesino sustentable del maguey papalote del Chilapan. Fase II. 9883 records from University of Nebraska State Museum Birds Collection. 78 records from Planktic foraminifera counts at CTD station PS55/079-1. 2 records from New Descriptions Of North American Taenionema Larvae (Plecoptera: Taeniopterygidae). 30349 records from University of California Santa Barbara Invertebrate Zoology Collection. 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 4 records from Discovery of the male of Colletes yanruae from Yunnan, China (Hymenoptera: Apoidea: Colletidae). 111 records from Birdrace-Uhulogen-Lippe. 17 records from Feral Pigs - Sightings and Cull records - 2018-2019. 1 records from First record of Gracixalus quyeti (Amphibia: Anura: Rhacophoridae) from Laos: molecular consistency versus morphological divergence between populations on western and eastern side of the Annamite Range. 4882 records from 台灣花蓮沿海賞鯨活動鯨豚觀測紀錄 (The observation records from the activities of whale and dolphin watching in the offshore of Hualien, Eastern Taiwan). 23 records from Calcareous dinocysts in ODP Hole 80-550B, part 2. 1640 records from La familia Asclepiadaceae en México. 5460 records from Colección de Fabales del Museo Botánico CORD - IMBIV. 3 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 3 records from Morphological and molecular characterization of Klossnema viguerasi n. sp (Nematoda: Oxyuridomorpha: Hystrignathidae) from a Cuban passalid beetle (Coleoptera: Passalidae), first record of the genus for Cuba. 137 records from Hartland Nature Club Lepidoptera Collection. 1 records from A taxonomic review of the genus Gibbotettix with description of one new species (Orthoptera: Tetrigidae). 86314 records from ALCB - Herbário Alexandre Leal Costa. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 114 records from BIRDRACE LiLaLau. 373 records from Otter survey of Ireland 2004 & 2005. 89875 records from Fish specimens of Kagoshima University Museum. 1056 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 3825 records from UTEP Invertebrates (Arctos). 1323 records from Fish occurrence in Kuban River basin. 73 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 249 records from Données opportunistes produites par Alexandre RUFFONI dans le cadre de l’élaboration d’un guide de détermination des larves de plécoptères. 1359 records from Happywhale - Gray Whale in North Pacific Ocean. 5 records from Two new day-flying species of Agrotis Ochsenheimer (Lepidoptera: Noctuidae) from the alpine summit of the Maunakea Volcano. 133152 records from Suivi Temporel des Rhopalocères de France (STERF). 15 records from New species of the genus Mimogonia and Holotrochus from South America (Coleoptera: Staphylindae: Osoriinae). 163 records from Relative abundance of coccosphere-units at site GIK23414. 134 records from Fossil specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 177 records from (Table 3) Abundance of planktonic foraminifera in ODP Hole 113-690C, large size fraction. 940 records from SeaTurtle surveys on Braamspunt by Green Heritage Fund of Suriname. 10 records from New species of Phaloria (Orthoptera: Phalangopsidae: Phaloriinae) from West Papua (Indonesia). 20 records from On the systematic status of Isopericlimenaeus Marin, 2012 and its type species, Periclimenaeus gorgonidarum (Balss, 1913) (Crustacea: Decapoda Palaemonidae). 181 records from UNCW Norfolk Canyon Aerial Survey - Left side - 2016. 38 records from Revision of freshwater shrimps belonging to Caridina weberi complex (Crustacea: Decapoda: Atyidae) from Polynesia with discussion on their biogeography. 3564 records from POPA- Fisheries Observer Program of the Azores: Turtle sightings in the Azores tuna fishery from 2000 on: during navigation or search mode.. 364 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 57 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 54 records from Bryophyte speciments of Toyota City Nature Sanctuari (TCNS).. 823 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 5 records from Three new species of deep-sea Gromia (Protista, Rhizaria) from the bathyal and abyssal Weddell Sea, Antarctica. 23 records from Abundance of benthos infauna at station GIK23042-2. 68 records from Streuobstwiese. 197 records from ABC_Event data recorded on a day trip to Mongolwe and Chikala Hills Forest Reserve, Machinga District. 659 records from Benthic foraminifera counts of sediment core GIK23352-3. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 47 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, >125 µm fraction. 247 records from Flora vascular y no vascular: expedición Cuenca Media del río Chicamocha - Proyecto Boyacá BIO UPTC. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 2779607 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 3 records from Gyrinus rhyssonotum sp. n., a new species of Gyrinidae (Coleoptera: Adephaga) from northern Brazil. 9 records from A New Species Of Novius Mulsant From New Caledonia (Coleoptera: Coccinellidae: Noviini). 1009 records from Programme ACT : Répartition Merle noir 2012 - 2016 Coordonnées GPS Lambert 93. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 1 records from Taxonomic novelties in Apocynaceae subfam. Asclepiadoideae from New Caledonia. 145 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/014-6. 5 records from Cave-inhabiting Neobisiidae (Arachnida: Pseudoscorpiones) from China, with description of four new species of Bisetocreagris Ćurčić. 4616 records from Inventaire de la flore du Grand Poitiers 2009. 31 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 1461 records from M. Gollop Collection. 5205 records from Collembola of Karelia: multiscale analysis of spatial distribution in pine forests. 1 records from Données naturalistes d'Olivier DELZONS. 140 records from Naturalis Biodiversity Center (NL) - Diptera. 95 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 1 records from A new species of Aphonopelma (Araneae: Mygalomorphae: Theraphosidae) from the Madrean pine-oak woodlands of northeastern Sonora, Mexico. 10 records from Epinephelus fuscomarginatus (Perciformes: Epinephelidae), a new species of grouper from off the Great Barrier Reef, Australia. 174 records from BIRDRACE Bon(n)apartemöwen. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 17 records from Plant-parasitic nematodes of Republic of Karelia. 1 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 4183 records from Marine Bird Sighting Data, Arctic Marine Biodiversity Observing Network (AMBON) Chukchi Sea research cruise on the vessel Norseman II from 2015-08-09 to 2015-09-03. 2099 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 3012 records from Distribution of foraminifera of sediment core GIK23258-2. 3 records from Taenionema Jeanae, A New Species Of Stonefly From Southern California (Plecoptera: Taeniopterygidae). 2534 records from Elaboration de table de tarif de cubage multispécifique (I). 521 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 38 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 16 records from Insect Collections of Okomu National Park- Nigeria. 279489 records from ARABEL - Arachnologia Belgica. 133637 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 412 records from Heinersdorfer Sumpfwiese. 8 records from Generic assignment of Leuciscus kurui Bogutskaya from the upper Tigris drainage, and a replacement name for Alburnus kurui Mangit & Yerli (Teleostei: Leuciscidae). 1 records from Capnia Shasta, A New Species In The Californica Group From Northwestern California (Plecoptera, Capniidae). 48 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-03. 348 records from Antarctic pycnogonids. 60962 records from MLZ Bird Collection (Arctos). 12 records from Leiocassis rudicula (Teleostei: Siluriformes: Bagridae), a new catfish from eastern Borneo. 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 2018. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 39 records from Northern Cyprus 2010 (aggregated per 1-degree cell). 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 385 records from University of Wyoming Museum of Vertebrates (UWYMV) Herpetology specimens. 14069 records from Midden-Limburg Fish Ponds Survey. 66051 records from Herbarium Senckenbergianum (FR) - Fungi. 1 records from A new species of Pristomerus Curtis, 1836 (Hymenoptera, Ichneumonidae Cremastinae) and key to the known species in Iran. 1994 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 160 records from Range table from benthic foraminifers in ODP Hole 189-1171C. 5 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1819 records from AMAPPS Northeast Aerial Cruise Summer 2016. 895 records from Geometridae de France métropolitaine. 18 records from Revision of the Palaearctic Trachusa interrupta species complex (Apoidea: Anthidiini) with description of four new species. 150 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 1 records from Revision of Family Megacalanidae (Copepoda: Calanoida). 1836 records from (Table 5) Distribution of calcareous nannofossils in ODP Hole 119-738C. 1290 records from Diversity of Spiders from Azorean Trails. 13442 records from United Kingdom National Whale Stranding Database 1913-2008. 4709 records from Dynamics of Collembola communities in a spruce-linden forest with mosses and sedges by layers (1973-1977). 10354 records from Inventaire de la flore de Charente-Maritime 2018. 2012 records from Pollen profile RAC20, Lake Racou, France. 4 records from Results of foraminifer and ostracode analyses of the Neogene of Hole 302-M0002A. 79 records from Chronicle of Nature - Phenology of Insects of Tigirek State Nature Reserve. 44 records from Oman 2008: Olive Ridley Turtles of Masirah (aggregated per 1-degree cell). 2 records from First record of the leafhopper genus Xenovarta Viraktamath (Hemiptera, Cicadellidae, Deltocephalinae) from India with description of a new species. 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 10283 records from Inventario de Hymenóptera; parasítica en México. 327 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 8561 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1785 records from 3Soil16S. 2 records from New and interesting palpigrades (Arachnida, Palpigradi) of the genera Koeneniodes Silvestri, 1913 and Prokoenenia Börner, 1901 from Asia. 715 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 9 records from New species and records of the Neoserica (sensu stricto) group (Coleoptera: Scarabaeidae: Sericini). 3 records from Holomorphology and Neotype designation of Microperla geei Chu, with egg morphology of Microperla qinlinga Chen (Plecoptera: Peltoperlidae). 30 records from Nannofossil abundance of Hole 24-233A. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 24 records from Dinoflagellate abundance of Hole 28-274. 27 records from Occurrence of mammalia relicts at site Biedermann. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1 records from The oldest representative of the modern snipe fly genus Symphoromyia (Diptera: Rhagionidae). 23136 records from PAH-contaminated sediment from the Lagos Lagoon, Nigeria. 27670 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 3 records from Description of a new species of the genus Cnemaspis Strauch, 1887 (Reptilia: Squamata: Gekkonidae) from the Nilgala Savannah forest, Uva Province of Sri Lanka. 276 records from Birds Specimens of Akita Prefectural Museum. 475 records from Planktic foraminifera counts of sediment core A15-558. 2 records from A new micropterous species of Leuctra (Plecoptera: Leuctridae) from the Lesser Caucasus (Georgia). 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 2 records from A new species of Phlogophora Treitschke (Lepidoptera: Noctuidae) from China. 100 records from Données naturalistes de LE GLOANEC Vincent. 213433 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-67, 1969-81. 10 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 185 records from Size of planktic foraminifera at CTD station PS55/051. 792 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 5260 records from Whale catches in the Southern Ocean. 230 records from Biometría peces Parque Nacional Natural La Paya. 2 records from Early myriapodous arthropods from Australia: Maldybulakia from the Devonian of New South Wales. 16 records from Assemblage of living benthic foraminifera in sediment core CD146_55921#1, 63-150 µm. 30 records from MVZ Herp Observations (Arctos). 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 4 records from Paragoniosomatinae, a new subfamily of Gonyleptidae (Arachnida: Opiliones) based on a new species from the Chapada Diamantina relict cloud forests, Brazil. 27867 records from MICA - Muskrat and coypu camera trap observations in Belgium, the Netherlands and Germany. 6 records from Foraminifera abundance of Hole 58-442. 108 records from MIRC NAVFAC Incidental Sightings - Aerial 1965-2014. 6 records from Potamotrygon boesemani (Chondrichthyes: Myliobatiformes: Potamotrygonidae), a new species of Neotropical freshwater stingray from Surinam. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 32 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 2 records from Two new species of the genus Sinodorcadion Gressitt, 1939 (Coleoptera: Cerambycidae: Lamiinae). 312 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 396 records from (Table 2) Species composition of algae and cyanobacteria encountered in plankton of the Large Aral Sea on June 2-8, 2008. 13 records from Coleção de Coleoptera da Universidade de Brasília. 1127 records from marine sediment metagenome Metagenome. 158115 records from The Himalayan Uplands Plant database (HUP Version 1). 10167 records from Observaciones de Aves asociadas a investigaciones de la Univerisdad ICESI en el periodo 2014-2019. 131 records from Artenvielfalt auf dem Schulgelände. 6173 records from SPC PROCFish/C Fish Observations New Caledonia 2004. 110 records from Range table from planktonic foraminifers in ODP Hole 177-1089B. 278 records from Gomex Sperm Whale Survey 2000. 10 records from Integrative taxonomy resuscitates two species in the Lasioglossum villosulum complex (Kirby, 1802) (Hymenoptera: Apoidea: Halictidae). 1 records from Siccia imana, a new species from Rwanda (Lepidoptera: Erebidae: Arctiinae). 86 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 30 records from Feral Pigs - Sightings and Cull records - 2014-2015. 1 records from On the systematic status of Calliophis macclellandi nigriventer Wall, 1908 (Reptilia: Serpentes: Elapidae). 50 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 63 records from Cetacean coordinated transborder monitoring using ferries as platforms of observation off Tunisia 2013-2014 - Atutax. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 20 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 1894 records from Fungi Collection. 2 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 87 records from Données espèces - Expertise IPE 70. 561 records from Colección Entomológica Universidad Nacional de Colombia, Sede Palmira (CEUNP). 1028 records from NOAA coral reef monitoring invertebrate data from sites across Micronesia from 2009-09-29 to 2015-09-25. 12 records from Two new genera and three new subterranean species of Hydrobiidae (Caenogastropoda: Truncatelloidea) from Tunisia. 3 records from A new species of the flower bug genus Orius Wolff (Hemiptera: Anthocoridae) cryptically inhabiting Hibiscus tiliaceus L. (Malvaceae). 20 records from A review of the genus Beltia Jacoby (Chrysomelidae: Eumolpinae: Eumolpini), with descriptions of fourteen new species from Costa Rica, Panama, and northwestern South America. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 30954 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 152 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 1 records from Happywhale - North Atlantic Right Whale in North Atlantic Ocean. 121 records from Total foraminifera counts of multinet M10/2_MSN262. 87151 records from NE AVH data. 98 records from Description of lithologic section units of IODP Hole 325-M0033A. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 21 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 48 records from Schulgelände (Wetter). 282 records from Deponie Klausdorf. 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 1224 records from University of Jena, Herbarium Haussknecht - Herbarium JE. 247 records from DUML vessel-based photo-id and biopsy surveys for proposed JAX USWTR site 2012-2015. 55 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 22800 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 1986 records from Observations de Coléoptères saproxyliques de Frédéric LACOSTE. 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 23 records from Benthic foraminifera abundance of Hole 42-379A. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 2 records from The species of Ctenopelma Holmgren (Hymenoptera, Ichneumonidae) from China. 1489 records from Population research on small rodents (Rodentia) and screws (Soridae) in Steinkjer Municipality – Norway; 2018 - 2019 based on systematic catches with ordinary mouse traps in traplines. 903 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 2548 records from BioGIS - Reptiles - HUJ collections. 13 records from Analyses of the recent components of sediment core PS1222-1. 901635 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 3 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 2 records from Two new species in the genus Andronymus Holland, 1896 (Lepidoptera, Hesperiidae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 43 records from Six new species of Anthuridae (Peracarida: Isopoda) from the southern Mexican Pacific. 2 records from Two new species of Hetereleotris (Perciformes: Gobiidae) from the Red Sea. 129 records from Données du/de la naturaliste jourdan christian provenant de la base de donnée du SINP Île-de-France CETTIA. 147 records from Revision of the spider genus Hoplopholcus Kulczyński (Araneae, Pholcidae). 754 records from Programme ACT : Répartition Grive draine 2001 - 2005 Coordonnées GPS Lambert 93. 1856 records from Analysis of macrobenthos in the Southern Bight of the North Sea (1971-1972). 186 records from Interstitial and parasitic Platyhelminthes from the coast of the Seychelles in 1992 and 1993. 10 records from Ostracoda abundance of Hole 32-306. 990 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 244 records from Nannofossil abundance of Hole 29-281. 3827 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 224 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 167 records from Ten new species of Phyllodoce Lamarck, 1818 (Phyllodocidae, Annelida) from Brazil. 159 records from Total foraminifera counts from multinet M31/3_MSN915. 41676 records from Tagged Seal Location Data from SOGLOBEC. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 333 records from Données naturalistes de Renaud PUISSAUVE. 839 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 9 records from Contribution to the Asian and Afrotropical species of the genus Dyschiriodes (Coleoptera: Carabidae: Scaritinae). 1748 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 1709 records from The Gibson spider collection. 56 records from Revision of the bee genus Bathanthidium Mavromoustakis (Hymenoptera: Apoidea Megachilidae: Anthidiini) with description of a new species from China. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 651 records from Réseaux écologiques/Trame verte et bleue. 460 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 2 records from Additions to the deep-sea echiuran (Echiura) fauna of the North-East Atlantic. 14 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 4 records from A new species of Neoperla (Plecoptera: Perlidae) from southeastern Tibet of China with additions to the knowledge of N. perspicillata Zwick, 1980. 66164 records from Florida Keys Reef Visual Census 1996. 18 records from Review of Scatimus Erichson (Coleoptera: Scarabaeidae) in Colombia with the description of a new species. 236480 records from Wild bees of Belgium. 22 records from Observations de tortues marines dans l'archipel de Saint-Pierre et Miquelon. 54 records from Données du/de la naturaliste Villalta Rémi provenant de la base de donnée du SINP Île-de-France CETTIA. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 550 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 304 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 48 records from Total foraminifera counts of multinet M6/7_MSN140. 9740 records from Royal British Columbia Museum Entomology Collection. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 33 records from Dinoflagellate abundance of Hole 81-552. 2 records from A new species of Macrothrix (Crustacea, Branchiopoda, Macrothricidae) from the Neotropics with description of the marthae-group. 8 records from A review of the Neotropical microcaddisfly genus Acostatrichia Mosely, 1939 with description of a new species from Brazil (Trichoptera: Hydroptilidae: Leucotrichiinae). 2110 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 5938 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 66 records from Loggerheads in the Tyrrhenian Sea (aggregated per 1-degree cell). 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 143 records from Agromyzidae (Diptera: Schizophora) in the state of Pará: new species and new records in Brazil. 8367 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 2985 records from Colección Entomológica CDMB. 6 records from NZCS Invertebrates New Collection After 1987. 1 records from Happywhale - Ringed Seal in North Atlantic Ocean. 16929 records from Lepidoptera (Specimens NRM). 198 records from Chronicle of Nature - Phenology of Birds of FSBI United Administration of the Lazovsky State Reserve and National Park Zov Tigra. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 489 records from Caracterización bionómica de zonas de dragado y de afección de obras en la Ría de Ferrol. 27799 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 56 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 22124 records from Tachinid Recording Scheme - GB and Ireland records. 5 records from Thoridae (Crustacea: Decapoda) can penetrate the Abyss: a new species of Lebbeus from the Sea of Okhotsk, representing the deepest record of the family. 3 records from Denitrification bacteria in sediment cores of Daya Bay, China. 6 records from Five new species of Nazeris Fauvel in Guangxi, China (Coleoptera, Staphylinidae, Paederinae). 5 records from Données naturalistes de Mikaël PAILLET. 4379 records from Wild Bee Specimens from Blueberry and Raspberry Farms in the Champlain Valley, Vermont, USA. 4607 records from Données de type contact en Guadeloupe. 79 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 4 records from A new, uniquely patterned spiny eel (Teleostei: Mastacembelidae) from southern Borneo, Kalimantan Tengah, Indonesia. 15 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 13 records from Analyses of the recent components in the sand fraction of sediment core PS1219-1. 245 records from Planktic foraminifera counts of sediment core V14-77. 2508 records from (Table 5) Eocene to Oligocene nannofossil range chart for ODP Hole 134-829A. 50 records from Herpetofauna de la expedición Pisba - Proyecto Boyacá BIO UPTC. 14 records from Taxonomic study of the genus Fujimacia Marumo, 1939 (Lepidoptera: Pyralidae) in China, with descriptions of four new species. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 267172 records from hymenoptera. 60 records from Amphibian and Reptilian (KIEE-AR). 4 records from Cast netting new species: Integrative taxonomy of Distichodus notospilus (Characiformes: Distichodontidae) discovers new species and overlooked areas of endemism in Central Africa. 1 records from New taxonomic and faunistic data on Asian species of the genus Indenicmosoma Ardoin (Coleoptera: Tenebrionidae: Lagriinae), with description of a new species from Thailand. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 1 records from Description of the larva of Meliboeus morawitzi (Semenov, 1905) (Coleoptera: Buprestidae). 65 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (79° N section). 5919 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 361 records from Nannofossil abundance of Hole 66-490. 135 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/043-4. 325 records from (Table 2) Abundance of ostracods in surface sediment samples from the Admiralty Bay, King George Island, West Antarctica. 130 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 330 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 478 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 1044940 records from CLICNAT Base de données naturaliste picarde gérée par Picardie Nature. 23 records from Review of Lepidocyrtinus Börner, 1903 (Collembola, Entomobryidae, Seirinae): the African species. 413272 records from DATAVES. 174 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 2 records from A cladistic approach for generic delimitation of Paracloeodes Day, Rivudiva Lugo-Ortiz & McCafferty, and Varipes Lugo-Ortiz & McCafferty (Ephemeroptera: Baetidae). 78 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 820 records from Nannofossil abundance of Hole 82-558A. 2 records from Taxonomic Studies on the Genus Myrmoteras Forel (Hymenoptera: Formicidae), with Description of Two New Species from India. 446 records from Programme ACT : Répartition Etourneau sansonnet 2006 - 2010 Coordonnées GPS Lambert 93. 3327 records from BioGIS - Mammals - SPNI. 3 records from Supplementary Illustrations For Two Nemoura (Plecoptera: Nemouridae) Species. 2 records from Description of a new species of Willemia (Collembola: Hypogastruridae) from Panama with key to Willemia species occurring in the Americas. 6 records from Planktic foraminifera abundance of Hole 53-418B. 510 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 14 records from Berea College, Ralph L. Thompson Herbarium. 13 records from Diatom abundance of Hole 60-460. 17 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 63-125 µm fraction. 18 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 409 records from Distribution of nanoplankton at trap WR2. 160 records from Range table from planktonic foraminifers in ODP Hole 180-1115C. 1 records from Glyptotermes chiraharitae n. sp., a new dampwood termite species (Isoptera: Kalotermitidae) from India. 50940 records from NOAA National Coral Reef Monitoring Program Benthic Percent Cover. 642 records from Flora vascular y no vascular:expedición El Consuelo - Proyecto Boyacá BIO UPTC. 7606 records from Lepidoptera of Mordovia State Nature Reserve. 2 records from First record of Trissolcus basalis (Hymenoptera: Scelionidae) parasitizing Halyomorpha halys (Hemiptera: Pentatomidae) in the United States. 3 records from Oxynoemacheilus shehabi, a new nemacheilid loach from the upper Orontes in southern Syria (Teleostei: Nemacheilidae). 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 141813 records from Fermanagh Flora. 130 records from Total foraminifera counts from multinet SO119_MSN1285. 163 records from Zostera noltei seagrass meadows spatial distribution at LTER site Ria de Aveiro lagoon in 2014. 1 records from First Record of the Ceratioid Anglerfish Species Gigantactis microdontis (Teleostei: Lophiiformes: Gigantactinidae) in the Western Pacific Ocean. 5883 records from MfN - Fossil vertebrates IV. 17 records from Marine metagenome ICM_AGW. 2 records from Two new species of Picicola Clay & Meinertzhagen, 1938 (Phthiraptera: Philopteridae) from Piciformes (Bucconidae and Galbulidae) in Brazil. 78 records from Données de la naturaliste Anna Even. 11 records from Happywhale - Peale's Dolphin in South Atlantic Ocean. 49 records from DECAF - AUTEC Sperm Whales - Multiple Sensors - Samples. 1607 records from MEXU/Flora de Oaxaca. 43391 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 816 records from Espèces végetales sur sable roux du fourré de Ranobe, PK 32 Toliara. 1 records from A new species of king cricket Glaphyrosoma Brunner von Wattenwyl, 1888 (Orthoptera: Anostostomatidae: Glaphyrosomatini) from Costa Rica with behavioral observations. 6445 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 609 records from (Table 11) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-713A. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 2 records from Swedish Malaise Trap Project (SMTP) - Pachyneuridae. 207 records from Nannofossil abundance of Hole 66-488. 92 records from (Table 2) Ostracoda abundances in sediment core PS2185-6 (Lomonosov Ridge). 81 records from Kystfuruskoger i Tysnes og Fusa. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 79 records from Diatom abundance of Hole 95-613. 2364 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 8 records from Die Bachspezies 2008/2009. 73 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 3 records from Review of the New World Notomicrus Sharp (Coleoptera, Noteridae) I: Circumscription of species groups and review of the josiahi group with description of a new species from Brazil. 4 records from Herbarium Senckenbergianum (FR) - Protista. 20 records from A new sand frog from Namaqualand, South Africa (Pyxicephalidae: Tomopterna). 68910 records from Données de l'Observatoire de la Faune de Bourgogne. 848 records from (Table 5) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-588. 255 records from Programme ACT : Répartition Perdrix rouge 2009 - 2013 Coordonnées GPS Lambert 93. 4389 records from Colección Herpetológica (Reptiles) del Museo de Historia Natural de la Universidad Industrial de Santander. 1930 records from Fungi of parks, forests and reserves of New Jersey, 2018. 114 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 5 records from Taxonomic review of the genus Paranisitra Chopard (Orthoptera: Gryllidae: Eneopterinae: Nisitrini) with description of a new species from Mindanao. 539 records from Phenological Center - Birds (Murmansk). 7 records from Range table from benthic foraminifers in ODP Hole 178-1096A. 100 records from Demosponges from the sublittoral and shallow-circalittoral (<24 m depth) Antarctic Peninsula with a description of four new species and notes on in situ identification characteristics. 67 records from Mammals of the Natural Laboratory of Peat-Swamp Forest, Sebangau, Central Kalimantan, Indonesia. 6466 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 197 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 320 records from Echinoderms from the Seaflower Biosphere Reserve. 198 records from Programme ACT : Répartition Alouette lulu 1996 - 2000 Coordonnées GPS Lambert 93. 100 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 837 records from Range table from benthic foraminifers in ODP Hole 172-1063A. 117 records from Nannofossil abundance of Hole 49-408. 4 records from Reassessment of the taxonomic status of Pseudopaludicola parnaiba (Anura, Leptodactylidae, Leiuperinae), with the description of a new cryptic species from the Brazilian Cerrado. 17 records from Analyses of the recent components of sediment core PS1011-1. 24 records from Redescription of Hypostomus carinatus (Steindachner 1881) (Siluriformes: Loricariidae) from the rio Amazonas basin in Brazil. 1 records from New record of the genus Baetiella Uéno, 1931 (Ephemeroptera: Baetidae) from India with description of a new species and new records for five species. 58 records from Données du/de la naturaliste Williamson Thomas provenant de la base de donnée du SINP Île-de-France CETTIA. 5 records from Discovered online: Hibiscus hareyae sp. nov. of sect. Lilibiscus (Malvaceae), threatened in coastal thicket at Lindi, Tanzania. 13 records from Planktic foraminifera abundance of Hole 19-185. 445 records from Oceanic Society's Marine Mammal Sightings in Belize 1992 - 2011. 4 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 6 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 13 records from Records Of Neoperlini (Plecoptera: Perlidae) From Brunei Darussalam And Sarawak, With Descriptions Of New Phanoperla Banks And Neoperla Needham Species. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 4 records from A Catalogue and Historical Study of the Odonata of Ecuador. 1 records from Happywhale - Indian Ocean bottlenose dolphin in Indian Ocean. 2779 records from Biodiversity of the Desna river valley and its tributaries. 1361 records from Códigos de barras de la vida en peces y zooplancton de México. 2 records from Tertiarius minutulus sp. nov. (Stephanodiscaceae, Bacillariophyta) - a new fossil diatom species from Lake Ohrid. 10 records from Description of six new large species of Argentinomyia Lynch-Arribalzaga, 1891 and redescription of Talahua fervida (Fluke, 1945) (Diptera, Syrphidae, Syrphinae). 5 records from Loricifera - SMF. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 32 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 833 records from Plant species from the sacred and community forests of Mono departement. 479121 records from KTP Ring Data. 103 records from Collection botanique Lamy de la Chapelle E. (BOUM). 12458 records from Brown University Herbarium. 89 records from Données du/de la naturaliste Le baron Gaetan provenant de la base de donnée du SINP Île-de-France CETTIA. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 95 records from BIRDRACE accipiter hardcore birding. 19317 records from Inventaire de la flore des Pyrénées-Atlantiques 2017 - Littoral. 71 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 324 records from Marine Mammal Observation - Total E&P Angola 2006-2011. 1 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 23 records from A revision of Eastern Palaearctic Anthobium Leach, 1819 (Coleoptera: Staphylinidae: Omaliinae: Anthophagini). II. fusculum group, and two additional species of the nigrum group. 17 records from The millipede genus Glomeris Latreille, 1802 (Diplopoda, Glomerida, Glomeridae) in North Africa. 1 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 143576 records from Happywhale - Humpback Whale in North Pacific Ocean. 712 records from POPA- Fisheries Observer Program of the Azores: Discards in the Azores tuna fishery from 1998 to 2013. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 2173 records from Interannual variability of ichthyoplankton diversity in the Patos Lagoon estuary Southern Brazil. 21 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 136 records from Swedish Malaise Trap Project (SMTP) - Heloridae. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 1 records from A new cave-dwelling Gekko (Gekko) from Lopburi Province, central Thailand (Squamata, Gekkonidae). 90 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 4 records from Discovery of the genus Kudakrumia Krombein, 1979 (Hymenoptera: Mutillidae) in India and description of a new species. 1 records from A new species of Liphistius from Myanmar and description of the actual male of L. birmanicus Thorell, 1897 (Araneae, Mesothelae, Liphistiidae). 588 records from artsprosjektet_51-14_ophiostomatoid_fungi. 201 records from Biodiversity of springs and rock seepages 2003. 10776 records from CEFS_16S_ITS. 11 records from Inventaire et regroupement de données Natura 2000. 1198 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina (Peces). 14 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 5 records from Heteragrion lencionii (Odonata: Heteragrionidae) sp. nov. from Serra de Itabaiana National Park, Northeastern Brazil. 8 records from Revision of the endemic Philippine Poeciloterpa Stål (Hemiptera: Cercopidae) with description of four new species. 127 records from Planktic foraminifera abundance of Hole 37-332. 521 records from Schanzenanlage Bergham. 74 records from Reptiles presentes en la colección herpetológica SINCHI de la expedición al Río Apaporis - Proyecto Colombia BIO. 22 records from Contributions to the study of the grasshopper (Orthoptera: Acrididae Gomphocerinae) courtship songs from Kazakhstan and adjacent territories. 833 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 170 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 72 records from Total foraminifera counts of multinet POS231/3_MSN1332. 160 records from AVJNF: Søholt Storskov, amphibian survey. 961 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 25 records from On the Staphylinidae of the Greek island Samothraki (Insecta Coleoptera). 3251 records from Characterizing bumble bee (Bombus) communities in the United States and assessing a conservation monitoring method. 9098 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (Abejas). 5 records from Satellite Tracking of Hawksbill Turtle in West Sumbawa, Indonesia (aggregated per 1-degree cell). 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 395 records from Nannofossil abundance of Hole 37-334. 59 records from Schulgelände SGD/Viersen. 1533 records from Données du/de la naturaliste ARNABOLDI Frédéric provenant de la base de donnée du SINP Île-de-France CETTIA. 1293 records from Flora genérica de las gramíneas del estado de Tlaxcala. 69 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 4 records from New records of phytoseiid mites from Mauritius Island (Acari: Mesostigmata. 5464 records from Natural History Museum Maastricht (NL) - Herbarium. 422 records from Mushrooms Flora of Nepal at Central Department of Botany, Tribhuvan University, Nepal. 9384 records from MZL Invertebrate Collections. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 352 records from Loup 2015 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 11 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 5 records from A new species of Pherbellia (Diptera: Sciomyzidae) from Iran. 161 records from Total foraminifera counts of multinet SO117_MSN1244. 485 records from Rothschild Giraffe occurrence records observed at Mwea National Reserve in Central part of Kenya. 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 6 records from First record of Nesomesochorinae (Hymenoptera: Ichneumonidae) from America north of Mexico with descriptions of two new species of Nonnus Cresson. 6990 records from Ethnobotanical surveys species in Benin (West Africa). 87 records from Hidden gems in museum cabinets: new species and new distributional records of Scolytodes (Coleoptera: Scolytinae). 5576 records from uncultured prokaryote Targeted loci environmental. 3 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 136 records from Inventaire faunistique de l'ENS des Parc des berges de Seine. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 6387 records from Données naturalistes de Monsieur LAFAGE Denis. 5 records from On the genera Ptiloneura Enderlein, Loneura Navás, and Loneuroides García Aldrete (Psocodea: ‘ Psocoptera’: Ptiloneuridae). 51 records from Coccoliths in sediment core GIK23065-3. 133 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 14 records from A review of the bats (Chiroptera) of the Republic of Congo, including eight species new to the country. 90 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 127 records from Freshwater crustaceans in Antarctic and sub-Antarctic lakes. 2141 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 9 records from A review of Solierella Spinola, 1851 (Hymenoptera, Crabronidae) from Iran with description of four new species. 196 records from Happywhale - Leopard seal in South Atlantic Ocean. 17 records from Analyses of the recent components of sediment core PS1219-1. 365 records from HBRG Invasive Non-native Plants Dataset. 253 records from EDP Foz-Tua: Riparian Birds (point counts) Ecological Monitoring Program [2011]. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 3240 records from Inventario florístico de la Sierra de Huautla, Morelos. 1 records from A new species of Neoscelis Schoch from Mexico (Coleoptera: Scarabaeidae: Cetoniinae: Goliathini) with new distributional records for the genus. 186821 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 35 records from New species of Pyrrhulina (Teleostei: Characiformes: Lebiasinidae) from the eastern Amazon, Pará, Brazil. 143568 records from Movement patterns of Peruvian Boobies off Isla Lobos de Tierra 2006. 16253 records from Birds Specimens. 468 records from Suivi de l'expansion du Frelon asiatique (Vespa velutina) : données espèces non cibles piégées. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 53 records from Planktic foraminifera abundance of Hole 23-227. 18465 records from DMNS Mammal Collection (Arctos). 35 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 1 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 66 records from Tortugas Marinas del Golfo de California (aggregated per 1-degree cell). 64 records from Bats of northeastern Vietnam. 1028 records from IBF Monitoring of Fungi. 231 records from Sagehen Creek Field Station (UC-Berkeley) - Birds. 13 records from A New Species Of Capnia Pictet, 1841 (Plecoptera: Capniidae) From Kyushu, Japan, With Description Of Male Drumming Signals. 4 records from Phylogenetic differentiation and taxonomic consequences in the Saurodactylus brosseti species complex (Squamata: Sphaerodactylidae), with description of four new species. 884 records from Diversité et distribution de quelques espèces de plantes agroforestières au Bénin. 1 records from A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia. 4 records from Psychotria niauensis sp. nov. (Rubiaceae), espèce calcicole endémique de la Polynésie française, décrite de l’atoll soulevé de Niau (Tuamotu). 61 records from Alien Species in Poland - Plants. 21 records from Taxonomic revision of Ceropegia sect. Huernia (Asclepiadoideae, Apocynaceae) in Saudi Arabia with three new combinations. 323 records from Données de VINCENT Alexis (SAPROX). 27 records from Review of the species of the genus Serrapinnus Malabarba, 1998 (Teleostei: Characidae: Cheirodontinae) from the rio Tocantins-Araguaia basin, with description of three new species. 20 records from Description of five new Wulfila (Araneae, Anyphaenidae) species from Mexico with comments on the taxonomy of the genus. 1 records from Happywhale - Green Sea Turtle in North Pacific Ocean. 15 records from Nannofossil abundance of Hole 10-93. 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 2997 records from MMS Seabird Ecology Study 1985. 1422 records from Données du/de la naturaliste Chevreau David provenant de la base de donnée du SINP Île-de-France CETTIA. 13 records from A new species of genus Cyana Walker, 1854 (Lepidoptera: Erebidae: Arctiinae). 56 records from Données de la structure Forêts en Aulnoye provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from A new species and two new records of the ground spider genus Apopyllus (Araneae, Gnaphosidae) from Paraguay. 38 records from Ours 2006 présence Occasionnelle Mailles 10km LAEA Réseau Ours brun ONCFS. 1184 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 1560 records from Pacific turtle tracks: Turtle-Safe Seas Project. 1809 records from BenthosChukchiFN762_1976_Falk5. 944 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 33 records from New and little-known sun-moth species from Australia (Lepidoptera, Castniidae). 1 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 89 records from Seven new species of the spider genus Matta Crosby from caves in the State of Minas Gerais, Brazil (Araneae, Tetrablemmidae). 70 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 23449 records from Port Phillip Bay Environmental Study Data 1992-1996 - benthic records. 2 records from A new crab-associated amphipod of the genus Isaeopsis Barnard, 1916 (Amphipoda Senticaudata: Ischyroceridae) from southern Chile. 240 records from Knechtweide (Kohlfurth). 3238 records from Butterflie Specimens of Yamaguchi prefectural Yamaguchi Museum. 90 records from MCP-Mamiferos - Coleção de Mamíferos. 11 records from Benthic macrofauna abundance of sediment core 12930-073. 336 records from Stable isotope data and sedimentology of core SO42-74KL. 54670 records from Tetraonid line transect surveys from Norway: Data from Fjellstyrene. 2 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9349 records from Harriet Irving Botanical Gardens (HIBG). 7 records from Revision of the genus Cobbionema Filipjev, 1922 (Nematoda, Chromadorida, Selachinematidae). 46092 records from Weed and native flora data for the Swan Coastal Plain. 62 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 9002 records from Uncultured Environmental Isolate Targeted loci environmental. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1482 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3079 records from Insectes Hyménoptères Scollidés de France. 1 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 736 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 13 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 6189 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 9 records from Occurrence of mammalia relicts at site Climauti II. 140 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 135 records from Waldi-Weiher. 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 25 records from Données de NICOLAS Vincent (SAPROX). 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 493 records from Fauna and population of oribatid mites (Acari, Oribatida) in the vicinity of Kosogorsky metal works (Tula Region, Russia). 1 records from Rhopalomenia glandulosa spec. nov., and the restoration of Entonomenia Leloup (Mollusca: Solenogastres). 6440 records from Microbial ecology of bacteiral community in sediment from adjacent waters of Rushan Bay. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 38 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 9 records from Planktic foraminifera abundance of Hole 14-144. 2572 records from seawater metagenome Metagenome. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 530 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 4372 records from Heliconiine Butterfly Collection Records from University of Cambridge. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 943 records from Programme ACT : Répartition Tourterelle turque 2012 - 2016 Coordonnées GPS Lambert 93. 16 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 508 records from Northern elephant seals post-molting 2017 (aggregated per 1-degree cell). 255 records from Tejidos colectados en el páramo de Pisba, Boyacá - Proyecto Boyacá BIO. 79 records from Birdrace-Bielefinken-Bielefeld. 4054 records from Fish specimens of Toyama Science Museum. 121 records from Range table from ostracoda in ODP Hole 143-866B. 6004 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 3529 records from A dataset from bottom trawl survey around Taiwan. 14237 records from Tachinid Recording Scheme - Tachinid fly records verified via iRecord. 4 records from Pheronema on the mid-Atlantic Ridge, data from NRCan. 140765 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 2080 records from Catopsilia butterfly specimens at Museum Zoologi Bogor, Indonesia. 8 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 1 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 11840 records from Coral Reef Evaluation and Monitoring Project Florida Keys 1998. 1 records from A mid-Cretaceous female scale insect (Hemiptera: Sternorrhyncha: Coccomorpha) in Burmese amber. 191 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 5 records from Copepoda (Siphonostomatoida: Dirivultidae) from Hydrothermal Vent Fields on the Central Indian Ridge, Indian Ocean. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 67 records from Post-nesting migration of loggerhead turtles around Japan 2005 (aggregated per 1-degree cell). 12 records from Lepidoptera specimen database of Japan. 37 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 273 records from Planktic foraminifera abundance of Hole 68-503B. 130 records from BIRDRACE - The famous Grouse feat. The James. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 7138 records from VIES herbarium - Universidade Federal do Espírito Santo - Herbário Virtual REFLORA. 294 records from Aves de la expedición en el páramo El Valle, Boyacá - Proyecto Boyacá BIO. 22 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 536 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 6 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 1 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 29 records from Occurrence of mammalia relicts at site Goyet Cave 3. 74 records from Anfibiofauna asociada a la quebrada Giginia, corregimiento de Doña Josefa, Municipio del Atrato - Chocó, 2019. 37 records from FBIP: scallop population genetics. 18 records from Schulgarten der Gesamtschule Am Heidberg. 12 records from New species of Condylostylus Bigot (Diptera: Dolichopodidae) from Comoros Madagascar, Tanzania and South Africa, with key to Afrotropical species. 1270 records from Données du/de la naturaliste Lantz André provenant de la base de donnée du SINP Île-de-France CETTIA. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 62 records from Données naturalistes de BONCHE Jérôme. 304 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 28 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 79758 records from natagora-earlybirds. 4 records from Happywhale - Spinner Dolphin in North Atlantic Ocean. 8985 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 16 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 29 records from Reptiles Specimens of Akita Prefectural Museum. 338 records from UWIZM Snakes. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 182 records from Tejidos colectados en el piedemonte llanero, Boyacá - Proyecto Boyacá BIO. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 449 records from Artsprosjekt Pyrenomycetes. 75152 records from NOAA coral reef monitoring benthic data from sites across Micronesia from 2009-09-29 to 2015-09-25. 121 records from Etude écologique du Parc des Lilas (94). 12 records from Données bibliographiques ASFRA. 34 records from Database of European river lamprey (Lampetra fluviatilis (Linnaeus, 1758)) actual samples deposited in the A.N. Severtsov Institute of Ecology and Evolution. 5061 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 1 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 2340 records from Butterflies of Singapore and Peninsular Malaysia (Nymphalidae). 6532 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 254 records from Atlantic Forestry Centre Insect Reference Collection. 123 records from Revision of the spider genus Mystaria Simon, 1895 (Araneae: Thomisidae) and the description of a new genus from the Afrotropical region. 583 records from Colección Ornitológica-Museo de Historia Natural Unillanos. 4 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 2252 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1 records from Two new genera and species of Fidicinini Distant, 1905 with a re-description of Nosola Stål, 1866 (Hemiptera, Auchenorrhyncha, Cicadidae). 462 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 1 records from World catalogue of the Hydrophiloidea (Coleoptera): additions and corrections II (2006 - 2010). 12118 records from Soil metagenome from healthy and unhealthy agricultural soil. 1478 records from Programme FLASH : Répartition Pluvier doré 2012 - 2016 Coordonnées GPS Lambert 93. 41 records from Morphologische Daten von Natrix. 3 records from A new species of Ahaetulla Link, 1807 (Serpentes: Colubridae: Ahaetullinae) from India. 2 records from New state and island records of Coccinellidae (Coleoptera) in Hawai‘i, USA. 46 records from Revision of the Garra species of the Hajar Mountains in Oman and the United Arab Emirates with the description of two new species (Teleostei: Cyprinidae). 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 55 records from Galls on Beech Trees in Hainich, 2008. 1000 records from SEFSC Mid-Atlantic Tursiops Survey, 1995 3. 6 records from New species of Anaptomecus Simon, 1903 (Araneae: Sparassidae) from Colombia, with an identification key for all known species of the genus. 31 records from Ecosystems of the sandstone region incl. sand-belt (SE of Melb.). 4 records from The Chinese species of the mealybug genus Neotrionymus Borchsenius (Hemiptera: Coccoidea: Pseudococcidae). 8 records from A new species of Cetopsis from the Guiana Shield (Siluriformes: Cetopsidae: Cetopsinae). 640 records from Annales de la Société Linnéenne de Maine-et-Loire. 1722 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 12451 records from Insectes Hétéroptères Mirides de France. 1 records from Happywhale - Long-finned Pilot Whale in North Pacific Ocean. 3 records from Taxonomic notes on the tribe Dryptini Bonelli, 1810 with description of a new genus and species from China (Coleoptera: Carabidae: Dryptini). 354 records from Programme ACT : Répartition Caille des blés 2000 - 2004 Coordonnées GPS Lambert 93. 561 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 618 records from Pollen analysis of sediment core GeoB6518-1. 494248 records from BLS Mapping Scheme dataset, 1750-2009. 1114 records from Chronicle of Nature - Phenology of Plants of Kronotsky Federal Nature Biosphere Reserve. 10 records from New plant associations for adults of some species of Acmaeodera Eschscholtz (Coleoptera: Buprestidae) occurring in the western United States. 27 records from Relative abundance of planktic foraminifera in sediment core K11. 27 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 620 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 275 records from Composición florística de áreas degradadas por actividad minera a cielo abierto en el municipio de Condoto-Chocó, como insumo para calcular la biomasa vegetal, 2017. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 1 records from Re-description of Grammapsychops lebedevi Martynova, 1954 (Neuroptera: Psychopsidae) with notes on the Late Cretaceous psychopsoids. 4755 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 21 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 165572 records from University of Tartu Natural History Museum and Botanical Garden Zooloogical Collections. 2 records from On species of the genus Macrosaldula (Hemiptera: Heteroptera: Saldidae) of the Palaearctic Region, with description of M. graziae sp. nov.. 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 7 records from Grundwasserlebensraum im Englischen Garten (München). 53 records from Description of lithologic section units of IODP Hole 325-M0043A. 208 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 2 records from Dilatapalochrus gen. nov. - a new species and a new genus of soft-winged flower beetle of the tribe Apalochrini (Coleoptera: Malachiidae) from East Africa. 19 records from Nesting biology and distribution of Stenancistrocerus (Paratropancistrocerus) obstrictus (Morawitz, 1895) (Hymenoptera: Vespidae: Eumeninae). 3 records from Description of a new species of the Rhinolophus trifoliatus-group (Chiroptera: Rhinolophidae) from Southeast Asia. 830 records from Invertebrados del Parque Nacional Arrecife Puerto Morelos. 7896 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 753 records from Colección de insectos de importancia médica del Instituto Nacional de Salud - Ceratopogonidae. 3 records from Prosoglypta, a new remarkable genus from Vietnam (Coleoptera: Staphylinidae: Omaliinae: Omaliini). 2873 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología (Mexicanos). 720 records from Données du naturaliste Bussac Augustin provenant de la base de donnée du SINP Île-de-France CETTIA. 4 records from Description of the previously unknown sexes in four West African Lycaenidae (Lepidoptera) with new data on their distribution. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 44050 records from Données naturalistes de Pascal Dupont. 18 records from suivi du site Natura 2000 Carrière Saint Nicolas. 2170 records from Inventaire des sangsues - détermination prélèvements de bureau d'études (qualité de l'eau) - Subvention UMS Patrinat. 310 records from Registros de macroinvertebrados acuáticos en un bosque seco del municipio de Honda. 90 records from Faunal assemblage of sediment core GS7603-13. 2 records from Wie viel Natur gibt es im Park?. 2 records from A new species of the fishfly genus Neochauliodes van der Weele (Megaloptera Corydalidae) from India. 598 records from Monitoreo de la abundancia, riqueza y biodiversidad de aves del Santuario de Flora y Fauna Galeras en 2019. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 2297 records from Colección de Anfibios. 1082 records from Zootaxa. 10979 records from NBMB Herps. 1 records from A new species-group of Clubiona Latreille, 1804 and descriptions of four new species from Borneo (Araneae, Clubionidae). 214 records from Caracterización de vertebrados terrestres en el Cerro Guadalupe, municipio de Manzanares. 96 records from Peces presentes en la colección ictiológica de la Amazonía Colombiana de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 53062 records from British Antarctic Survey Argos satellite tracking data. 3763 records from Empire Wind Digital Aerial Wildlife Surveys for BOEM Lease Area OCS-A 0520, Equinor Wind US LLC, November 2017-October 2018. 431 records from An annotated checklist of Belgian Therevidae (Diptera, Asiloidea). 21 records from Taxonomic notes on the Polistes stigma group (Hymenoptera, Vespidae: Polistinae) from continental Southeast Asia, with descriptions of three new species and a key to species. 231786 records from Soil bacterial diversity is associated with human population density in urban greenspaces. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 113 records from Total foraminifera counts of multinet M26/1_MSN844. 18 records from Taxonomic status of Macaronesian Eucyclops agiloides azorensis (Arthropoda: Crustacea: Copepoda) revisited - morphology suggests a Palearctic origin. 7 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 2679 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 5856 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 583 records from Données du naturaliste Christian Desmier. 9 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 836 records from Odoanta of Akwa Ibom State University, Nigeria. 1134 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 189 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 11884 records from Données naturalistes de Franck NOEL. 1 records from Systematic revision of Calligrapha s. str. Chevrolat (Coleoptera: Chrysomelidae, Chrysomelinae). 2 records from A new Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) from the northern Western Ghats, Maharashtra, India. 364 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2369 records from Chronicle of Nature - Phenology of Birds of Darwin Nature Biosphere Reserve. 27 records from The Neotropical species of the genera Pseudespeson L, 1994 and Espeson S, 1882 (Coleoptera: Staphylinidae: Osoriinae). 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 111 records from Review of Afrotropical Glenosema Kieffer (Hymenoptera, Bethylidae) with description of 13 new species. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 150 records from Planktic foraminifera abundance of Hole 94-610B. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 2082 records from Registros biológicos de flora para el desarrollo de acciones de evaluación, seguimiento y monitoreo en los elementos priorizados de la estructura ecológica principal del distrito capital. Bogotá D.C.. 196 records from Arizona State University Lois B. O'Brien Collection. 40 records from Occurrence of mammalia relicts at site Zigeunerfels. 2 records from Description of lithologic section units of IODP Hole 325-M0052C. 97 records from Amphibiens filet/Marbotte-Ronval 2013. 47 records from Black Corals (Anthozoa: Antipatharia) from the Southwestern Atlantic. 3319 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 7178 records from Ravensthorpe Range survey data. 5 records from Scorpaena regina, a new scorpionfish (Teleostei: Scorpaenidae) from the east coast of Queensland, Australia. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 84 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 5 records from Schulinnenhöfe (Gelsenkirchen). 16 records from New species of Adeonellopsis (Bryozoa: Adeonidae) from southern Zealandia and the western Tasman Sea. 36 records from The Italian species of the Chthonius ischnocheles group (Arachnida, Pseudoscorpiones, Chthoniidae), with reference to neighbouring countries. 318 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 5 records from Two new species of Eumeninae from Iran (Hymenoptera: Vespidae). 2933 records from Données naturalistes d'Alain BERLY. 27676 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 8 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 12 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 368 records from Ring ouzel national sample survey in the UK in 1999. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 18 records from Two new desma-less species of Theonella Gray, 1868 (Demospongiae: Astrophorida: Theonellidae), from the Great Barrier Reef, Australia, and a re-evaluation of one species assigned previously to Dercitus Gray, 1867. 222 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Fishs. 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 7484 records from Yoann_BLANCHON_2017_12_18. 60 records from Assemblage of living benthic foraminifera in sediment profile GeoB4913-4. 250 records from Inventaire et regroupement de données Natura 2000. 89 records from Meniscus Midges (Dixidae) of Ireland. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 286 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1748 records from Occurrence database of native plants and animals of south-central Chile. 259 records from Natura 2000 Parc naturel régional de Lorraine. 25 records from Sierraperla Jewett, 1954 (Plecoptera: Peltoperlidae), Distribution, Egg Morphology And Description Of A New Species. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 2 records from Hangzhou-sediment-sample Raw sequence reads. 208 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 6 records from Four new crane fly species of subgenus Tipula (Vestiplex) (Diptera, Tipulidae) from China. 243 records from Fish species occurrences from selected near shore and riverine habitats in Lake Edward (2019). 264 records from Swedish Malaise Trap Project (SMTP) - Mycetophilidae, Keroplatidae. 2 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 24 records from Review of the Taiwanese Laccobius Erichson, 1837 (Coleoptera: Hydrophilidae) with description of a new species. 2271 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 1677 records from The Belgica 121 expedition to the Western Antarctic Peninsula: a high resolution biodiversity census. 32 records from Happywhale - Killer Whale in Arctic Ocean. 1 records from Two new species of Plutomurus Yosii (Collembola, Tomoceridae) from the Caucasus. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 3 records from Euhampsonia rubricata spec. nov., a new moth species from northeastern India and western Myanmar (Lepidoptera: Notodontidae). 81 records from BCCM/ULC Cyanobacteria culture collection at the University of Liège (ISO9001 certified). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 1800 records from Données de la collection Rousset -1947-2013. 57 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 874 records from Programme ACT : Répartition Grive musicienne 2004 - 2008 Coordonnées GPS Lambert 93. 134 records from Lynx 2005 présence Occasionnelle Mailles 10km Réseau Loup-Lynx ONCFS. 87 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 90 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 12094 records from Amino acid addition experiment Metagenome. 3131 records from Données DREAL Centre-Val de Loire - Faune - 2018. 1 records from Morphological and molecular evidence of a new species of Melanochlamys (Gastropoda: Heterobranchia) from the Bohai Sea, China. 580 records from Rare plants database extract from Scottish Natural Heritage. 11 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 194 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 68377 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27220 records from Formidabel; Belgian Ants Database. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 55 records from Macroinvertebrados bentónicos de playas de arena (Monte Hermoso-Pehuen Có, Buenos Aires, Argentina). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 2352 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 119 records from Suivi des leucorrines sur le site du Marais du Plata. 39621 records from ALCB herbarium - Universidade Federal da Bahia - Herbário Virtual REFLORA. 29986 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Vascular Flora and Habitats: species of conservation concern (RELAPE) - [2010-2014]. 4 records from Laminatubus (Serpulidae, Annelida) from eastern Pacific hydrothermal vents and methane seeps, with description of two new species. 127 records from Сypripedium guttatum Sw. in the Komi republic. 146 records from Abundance of birds in the Lena Delta Region. 31 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 54 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 7 records from Descriptions Of The Adult Male And Female Genitalia Of The Genus Osobenus Ricker (Plecoptera: Perlodidae). 433 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 35 records from Ortsrand Zandershagen. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 2 records from Happywhale - Southern Right Whale Dolphin in South Atlantic Ocean. 31 records from Planktic foraminifera counts of sediment core V19-21. 69 records from artsprosjektet_48-13_monomyx. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 1188 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 5360 records from Colección Ornitológica de la Universidad del Valle. 794 records from USWTR JAX Aerial Survey -Right side- 2009-2010. 338 records from Chronicle of Nature - Phenology of Plants of State Nature Reserve Privolzhskaya Lesostep. 10 records from Discoveries of the genera Baeochila and Idiocysta from Japan, with descriptions of two new species (Hemiptera: Heteroptera: Tingidae). 1 records from Museo Historia Natural UNAH VS (MUVS) Fish Collection. 1668 records from The ‘ red-tailed’ Lasioglossum (Dialictus) (Hymenoptera: Halictidae) of the western Nearctic. 9956 records from Fungal literature records database of the Southern West Siberia (Russia). 188 records from Données de Mammifères marins. Mission Sanctuaire AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 1 records from Notes on the genus Gargela (Lepidoptera: Crambidae) ı with descriptions of two new species from China. 12719 records from Données bibliographiques et opportunistes Mammifères du Nord Pas-de-Calais issues du SIRF. 637617 records from Données de la flore d’Alsace (SBA). 1012 records from Programme ACT : Répartition Merle noir 2000 - 2004. 3 records from MSB Mammal Observations (Arctos). 2 records from Pygmy grasshoppers of the genus Formosatettix Tinkhamı 1937 (Orthoptera: Tetrigidae: Tetriginae). 486 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 39 records from HRC CRC Small Vessel-Based Monitoring Surveys October 2009. 872 records from Typotheca of the higher vascular plants stored in M.G. Popov Herbarium (NSK) at the Central Siberian botanical garden SB RAS. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 10 records from Données naturalistes de Sophie COHEN. 696 records from the diversity of anammox bacteria in the subterranean estuary. 53 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 160 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données Mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 1. 2 records from The spider wasp genus Telostholus Haupt, 1929 (Hymenoptera, Pompilidae) in Malaysia, with the description of four new species. 141 records from NEON Biorepository Zooplankton Collection (Unsorted Bulk Sample). 384 records from Nannofossil abundance of Hole 17-167. 176 records from Paguroids (Decapoda: Anomura: Diogenidae and Paguridae) of the remote oceanic Archipelago Trindade and Martin Vaz, off southeast Brazil, with new records, description of three new species and zoogeographical notes. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 1879 records from Database of Australasian Vertebrate Occurrences. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 498 records from Bekkelag basin, Inner Oslofjord. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 2023 records from Composición florística y estructura vegetal de una parcela permanente en un relicto de bosque seco tropical en el Caribe colombiano. 34 records from Oman 2008: Green Turtles of Masirah (aggregated per 1-degree cell). 748 records from Phenological Center - Birds (Laplandskiy). 1 records from Cabdio crassus, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Kaladan River of Mizoram, India. 609 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 18 records from Four Species of Dulichiidae (Crustacea: Amphipoda) from Japan, with the Description of a New Genus and Two New Species. 36 records from Benthic foraminifera abundance of Hole 42-380. 57 records from Inventaire faune flore de l'étang d'Abbecourt à Orgeval. 9 records from Revision of Pseudexogone Augener, 1922 (Annelida, Polychaeta, Syllidae), and its transfer to Pilargidae. 110511 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 423 records from Programme ACT : Répartition Caille des blés 2008 - 2012 Coordonnées GPS Lambert 93. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 1010731 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 60 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 3 records from A new species and new record of the genus Discoelius Latreille, 1809 (Hymenoptera Vespidae: Eumeninae) from China. 237 records from Virginia CZM Wind Energy Area Survey- Left side - January 2014 through March 2016. 58 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 1477 records from (Appendix A) Radiolarian abundances in ODP Hole 175-1084A. 1555478 records from Flore Franco-Belge. 16605 records from EAC - Herbário Prisco Bezerra. 30486 records from Marine Biological Sample Database, JAMSTEC. 1485 records from (Table 1) Distribution of early late Eocene fossil content in ODP Hole 115-715A. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 399 records from Otter (Lutra lutra), Outer Hebrides. 2 records from A new species of Hemacroneuria and additions to Chinoperla (Plecoptera: Perlidae) from China. 1531 records from Leif Richardson Vermont Bee Specimens. 63 records from The type specimens of bees (Hymenoptera, Apoidea) deposited in the Zoological Institute of the Russian Academy of Sciences, St. Petersburg. Contribution II. Family Halictidae, subfamilies Rophitinae, Nomiinae, and Nomioidinae. 9 records from PRA Sonneur à ventre jaune - étude de répartition. 10860 records from Collection Crustacea - ZMB. 874 records from The Living Murray Fish data. 740 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 4 records from Strepsiptera from Colombia: First record of the genus Strichotrema Hofeneder (Myrmecolacidae) and a new host-parasitoid association with Megalomyrmex cyendyra (Hymenoptera: Formicidae). 4428 records from "Categorization of the wild food plants and their importance for primate development in the natural forest of Akpe (Lama) in southern Benin.". 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 66 records from (Tab. 5) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 41-367, Cape Verde Basin. 6164 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 10 records from Données naturalistes de CLERGET sylvie. 86 records from Range table from benthic foraminifers in ODP Hole 172-1060A. 2 records from A new genus and species of grasshopper from China (Orthoptera: Acrididae Catantopinae). 13 records from Warnowufer Groß Klein. 7 records from Stadtrandlandschaft Apolda-Nord. 412 records from Algas pardas (Ochrophyta: Phaeophyceae) de la colección ficológica "Germán Bula Meyer", de la Universidad del Magdalena. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 109 records from Planktic foraminifera abundance of Hole 18-181. 40 records from Calliostomatidae, Colloniidae, Margaritidae, and Solariellidae (Gastropoda: Trochoidea) collected by the Marion Dufresne (MD 55) expedition in southeastern Brazil, with description of a new species of Calliostoma. 3 records from On the diversity of Terebellides (Annelida, Trichobranchidae) in West Africa, seven new species and the redescription of T. africana Augener, 1918 stat. prom.. 165 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 18539 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 1 records from BOTU-Fungi - Herbário Irina Delanova Gemtchújnicov - Coleção de Fungos. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 2 records from First description of male of the type species Parosmylus prominens Needham, 1909 (Neuroptera: Osmylidae) from India. 29 records from Sea Turtles of Nicaragua's Pacific Coast (aggregated per 1-degree cell). 7 records from Notes on slender species of the long-jawed spider genus Tetragnatha (Araneae Tetragnathidae) with description of three new species. 237 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocapra americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 1528 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1 records from Taxonomic morphology of the genus Adineta (Rotifera: Bdelloidea: Adinetidae) with a new species from a suburban garden. 322193 records from Florida Keys Reef Visual Census 2010. 3 records from Immature stages and biology of the enigmatic oxyporine rove beetles, with new data on Oxyporus larvae from the Russian Far East (Coleoptera: Staphylinidae). 153 records from annex1. 123 records from Total foraminifera counts of multinet POS247/2_MSN1377. 343 records from Programme ACT : Répartition Caille des blés 2012 - 2016 Coordonnées GPS Lambert 93. 28 records from Dinoflagellate abundance of Hole 28-270. 10 records from Two new endangered species of Polygala series Trichospermae (Polygalaceae), endemic to the Cerrado domain, Tocantins State, Brazil. 693 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 2 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 62 records from Rare vascular plant species in North-West of Kostroma region, Russia. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 5 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 17 records from New records of Cerambycidae (Coleoptera) for New Brunswick, Nova Scotia, and Prince Edward Island, Canada. 33560 records from Extracellular DNA marine sediment Targeted Locus (Loci). 2 records from Microfossil abundance of Hole 21-208. 1680 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 150 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 2 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 2041 records from marine metagenome Targeted Locus (Loci). 1 records from Occurrence of mammalia relicts at site Ejstrup. 333 records from (Table 1) Relative abundances of planktic foraminifera across the K/T transition in ODP Hole 119-738C on the Kerguelen Plateau, Indian Ocean. 24493 records from Plan de vertebrados de la Patagonia. 61 records from Planktic foraminifera distribution of sediment core TRI171-27. 3 records from Triplophysa sanduensis, a new loach species of nemacheilid (Teleostei: Cypriniformes) from South China. 6 records from Four new species of the genus Pseudosubhimalus (Hemiptera: Cicadellidae) from the Indian subcontinent. 332 records from Swedish Malaise Trap Project (SMTP) - Sepsidae. 22 records from Description of lithologic section units of IODP Hole 325-M0054B. 12869 records from Apoyo a las colecciones biológicas de la Facultad de Ciencias de la UNAM: Fase 1 (FCME_AL). 2554 records from AlgaTerra. 735 records from (Table 2) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-747A. 174 records from Planktic foraminifera abundance of Hole 22-217. 2 records from Occurrence of mammalia relicts at site Igstadt I. 107 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 1 records from Reclustering the cluster flies (Diptera: Oestroidea, Polleniidae). 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 1144 records from MfN - Fossil vertebrates III. 13000 records from LPO_PACA_2017_12_18. 8 records from Nannofossil abundance of Hole 39-353A. 342 records from Foraminifera distribution of sediment core KS310. 14181 records from Index Site Surveys Data for Olympia Oysters, Ostrea lurida, in British Columbia – 2009 to 2017. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 11131 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 2970 records from Distribution patterns of subtidal macrobenthos in the Tsitsikamma National Park. 94 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 104 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 405 records from NHMO DNA Bank Other groups collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 11 records from Barsine insolita, a new species from Indochina and India (Lepidoptera, Erebidae, Arctiinae). 4 records from IMMS Ridley 9 (aggregated per 1-degree cell). 42 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 2 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 3 records from El género Aleuroparadoxus Quaintance y Baker 1914, con descripción de tres nuevas especies, nuevos registros y clave para las especies (Hemiptera: Aleyrodidae). 463 records from Damselflies of the genus Argia (Odonata: Coenagrionidae) from Ecuador with descriptions of five new species. 3 records from Description of Bradinopyga konkanensis sp. nov. (Odonata: Anisoptera Libellulidae) from the coastal region of Maharashtra, India. 192291 records from University of Michigan Museum of Zoology, Division of Birds. 811 records from Données naturalistes de AUNEAU Florent. 1806 records from uncultured marine picoeukaryote strain:Peuk_V4_NWP2 Raw sequence reads. 494 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 5 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 1 records from Taxonomic revision of the Afrotropical scarab beetle genus Cerhomalus Quedenfeldt, 1884 (Coleoptera: Scarabaeidae: Orphninae). 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 408 records from Collection Graptolithina fossil SMF. 10 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 25934 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 10 records from Talitrid amphipods from India, East Africa and the Red Sea (Amphipoda, Senticaudata, Talitroidea, Talitridae). 11 records from Suphisellus grossoi sp. n., a new burrowing water beetle from South America and notes on S. flavolineatus (Régimbart, 1889) and S. grammicus (Sharp, 1882) (Coleoptera: Noteridae). 62 records from Zoo Frankfurt. 203 records from Estrategia de conservación de grandes felinos en el departamento del Meta. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 1085627 records from Fungal Records Database of Britain and Ireland. 1 records from Pandanipora fragilis-a new deep-water cyclostome bryozoan from the subequatorial Mid-Atlantic Ridge, Atlantic Ocean, and a review of Pandanipora worldwide. 2 records from Two new species of Sinacroneuria Yang & Yang, 1995 (Plecoptera: Perlidae) from Guizhou, southwestern China. 738 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 12984 records from La familia Asteraceae en México. Fase VI. 505 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 128 records from Données espèces - Expertise IPE 10. 63 records from Marine gastropod distribution from patagonian shallow waters. 1832 records from Distributional data on high altitude endemic taxa of vascular plants from western Balkans. 1 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 19 records from New species of Otiothopinae (Araneae: Palpimanidae) from Colombia. 18 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 13 records from The genus Anacroneuria Klapálek, 1909 (Plecoptera: Perlidae) from Maranhão State, northeastern Brazil. 204 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 16 records from Dinoflagellate cysts of surface sediments. 5 records from Collection Malakologie - SMNG. 50 records from Données d'observation de phanérogames marines en Martinique. 1 records from Rocky-intertidal cheilostome bryozoans from the vicinity of the Sesoko Biological Station, west-central Okinawa, Japan. 1721 records from Phytoplankton data collected from the Black Sea during November 1957 (Cruise 2). 145 records from Nannofossil abundance of Hole 67-499. 374 records from Coastal and Marine Species Database. 900 records from Convention Fédération française de golf - MNHN 2016-2019.. 212 records from NHMD Amber Collection. 164 records from Marybio Foundation marine mammal shipboard sightings in Bahia San Antonio, Patagonia 2008-2010. 224 records from Données du naturaliste DESCHATRE Thierry provenant de la base de donnée du SINP Île-de-France CETTIA. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 103 records from Bat diversity data by Formosan Golden Bat's Home. 222 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 9 records from UTEP Fish (Arctos). 5 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 138 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 79 records from Etude d'état initial de la biodiversité dans le cadre des EIES sur les plateaux situés dans la zone sud (Pompo) de la concession minière de Guinea Alumina Corporation(GAC) dans la region de Boké (CESP2016-022). 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 1066 records from Densidad poblacional para fauna medida por medio de cámaras trampa en los Valores Objeto de Conservación (VOC) del territorial Andes Occidentales. 860 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos silvopastoriles - Unillanos 2019. 4306 records from Saproxylic and herbivorous beetle species in old near-natural and old managed forests in south-eastern Norway. 1 records from A review of the species of Anaspis (s. str.) similar to A. nigripes Brisout and A. apfelbecki Schilsky, with the description of three new species (Coleoptera: Scraptiidae). 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 10 records from New species of Clavigeritae (Coleoptera: Staphylinidae: Pselaphinae) from Malawi and South Africa. 3766 records from Benthic foraminifera distribution of sediment core GIK17957-2. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 2 records from Potamocloeon edentatum sp. n. from Usambara Mountains in Tanzania (Ephemeroptera, Baetidae). 230 records from Porifera diversity and distribution data in the Southern Gulf of Mexico. 84 records from Colección de Hongos del Museo de Historia Natural Marina de Colombia – Makuriwa (Invemar). 1 records from Description on Solitudes dushengi gen. et sp. nov. from Xinjiang, China (Araneae: Gnaphosidae). 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 1625 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 12 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 22 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 3655 records from JOI - Herbário Joinvillea. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 20 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 27 records from A revision of the African wolf spider genus Amblyothele Simon. 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 4 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 81 records from Birdrace-Die_Ornithomaten-Herford. 1080 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 1 records from A new genus and species of Apameini (Lepidoptera: Noctuidae) from Sichuan (China). 84979 records from NINA Vanndata fisk. 103 records from Mammals (UWEP-MM). 1 records from A new species of Coleophora (Lepidoptera: Coleophoridae: Coleophorinae) from the Galápagos Islands, Ecuador. 7 records from Liogenys Guerin-Méneville, 1831 (Coleoptera: Scarabaeidae: Melolonthinae Diplotaxini) of northern South America and Central America: taxonomic overview with four new species. 510 records from Inventaires des cygnes du département de l'Eure. 25 records from Herpetofauna de la expedición Piedemonte Llanero - Proyecto Boyacá BIO UPTC. 47 records from Abundance and community structure of birds breeding in Kalahari woodland used as rangeland. 478 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 30 records from Jasus caverum (Crustacea: Decapoda: Palinuridae) from the eastern South Pacific Ocean. 165 records from HSU Vertebrate Museum Mammals Collection. 42 records from Moniliophyta del Herbario BAB (Instituto de Recursos Biológicos CIRN-INTA). 13 records from Nannofossil abundance of Hole 9-80. 30 records from Revision and phylogeny of the genus Andocaeculus (Acari: Caeculidae) I: the A. weyrauchi species group. 10 records from Umbyquyra gen. nov., a new tarantula spider genus from the Neotropical region (Araneae, Mygalomorphae, Theraphosidae), with a description of eight new species. 37445 records from ADDOMEx. 43 records from Review of the Oxynoemacheilus tigris group with the description of two new species from the Euphrates drainage (Teleostei: Nemacheilidae). 10907 records from Census of species recorded during phytosociological surveys in Benin. 1 records from The InBIO Barcoding Initiative Database: Wesmaelius (Kimninsia) nervosus (Neuroptera, Hemerobiidae): a new species of brown lacewing for the Portuguese fauna. 724 records from Programme ACT : Répartition Faisan commun 2009 - 2013 Coordonnées GPS Lambert 93. 305 records from Foraminifera abundance of Hole 57-440B. 117 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 64 records from (Table 4) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides and Pseudoschackoina saundersi in the upper part of the Calabianca section. 6241 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 2 records from Hydroporus novacula sp. n. from Georgia (Caucasus) (Coleoptera, Dytiscidae Hydroporini) - the first terrestrial species of the genus?. 245 records from Informatisation des carnets de terrain de Georges Catherine. 333 records from (Table 4) Relative abundance of some planktonic foraminifera and fragmentation ratios for ODP Hole 117-728A samples. 98734 records from Acoustic monitoring data of avian species inside and outside the evacuation zone of the Fukushima Daiichi power plant accident. 13 records from North Cyprus 2015 - Green Turtles (aggregated per 1-degree cell). 40 records from Sightings for Airborne Mine Neutralization System Aerial Monitoring in the NSWC PCD Study Area from October 2011, 2012. 26443 records from UTEP Insects (Arctos). 5364 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 626 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 1 records from Revision of the Genus Schizoretepora (Bryozoa, Cheilostomatida) from the Atlantic-Mediterranean region. 10 records from Données naturalistes de DURON Cyril. 15183 records from Collection Pisces SMF. 2691 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2016. 41552 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 1 records from Nomenclatural changes in the planthopper tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae), with the description of a new genus and a new species. 1366 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 11 records from NMML Harbor Porpoise Aerial Survey, Cook Inlet, 1991. 39 records from Inventaire Faune. 3 records from On the identity of Cyphonoxia maljuzhenkoi Zaitzev, 1928 (Coleoptera Scarabaeidae: Melolonthinae). 31 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 1538 records from Results of the pollen analysis of the Dyanushka peat sediments K7/P2. 208 records from Registros de arañas en el marco del proyecto Influencia de la dieta sobre la toxinología y toxicología en arañas. 36 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 1 records from Revision of the genus Carybdea (Cnidaria: Cubozoa: Carybdeidae): clarifying the identity of its type species Carybdea marsupialis. 30 records from The larva of Amphigomphus somnuki Hämäläinen, 1996 and the first records of the genus Stylogomphus Fraser, 1922 for Thailand (Odonata: Gomphidae). 133 records from Planktic foraminifera abundance of Hole 42-375. 70 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 4 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 17827 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 242 records from Landschaftspflegehof (Berlin). 7 records from Four new species of giant pill-millipedes from Vietnam (Sphaerotheriida, Zephroniidae). 1553 records from University of Valencia cetacean surveys in the Spanish Mediterranean 2000-2003. 31 records from Planktic foraminifera abundance of Hole 32-305. 6 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 14346 records from Estado actual, identificación de riesgos y propuestas para el manejo de las especies invasoras presentes en las regiones hidrológicas prioritarias, confluencia de las Huastecas, Media Luna y Cabecera del río de La Laja. 51 records from Total foraminifera counts from M35/1_MSN1051. 1514 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 6 records from Review of the genus Shilovia Makarchenko (Diptera: Chironomidae: Diamesinae Boreoheptagyiini) from the mountains of Central Asia, with morphological description and DNA barcoding of known species. 2 records from The new genus Habeastrum, with two new species (Gastropoda, Diplommatinidae) in Mato Grosso do Sul caves, Brazil. 4 records from Sponges of the family Esperiopsidae (Demospongiae, Poecilosclerida) from Northwest Africa, with the descriptions of four new species. 10 records from Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae). 6782 records from Odonata de Veracruz. 85 records from Range table from benthic foraminifers in ODP Hole 178-1097A. 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 326 records from Scorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 502 records from AMAPPS Southeast Aerial Cruise Spring 2014. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 1319 records from Inventaire et suivi Avifaune. 934 records from Botanic Garden of the Finnish Museum of Natural History. 20 records from Happywhale - Sei Whale in South Pacific Ocean. 79 records from Planktic foraminifera abundance of Hole 63-470A. 7653 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 459 records from Marine Mammal Observation - Total Denmark 2013-2020. 1 records from A new species of Sphaeridium from northeastern India and Myanmar (Coleoptera: Hydrophilidae: Sphaeridiinae). 43 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 6 records from A new species of Notacanthurus Tshernova, 1974 (Ephemeroptera: Heptageniidae) from India. 3 records from A new species of Isoperla (Plecoptera: Perlodidae) from the Qinling Mountains of northwestern China and notes on the Chinese species of the genus. 35 records from Variability and distribution of the golden-headed weevil Compsus auricephalus (Say) (Curculionidae: Entiminae: Eustylini). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 21 records from Observations of three Idotea species (I. balthica, I. chelipes and I. granulosa) in Northern Europe, including the Baltic Sea - field data. 20 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 1596 records from EDP Baixo Sabor: Construction and Reservoir Filling Phases – Wolf, (Canis lupus) Wild Boar (Sus scrofa) and Roe Deer (Capreolus capreolus) [camera-trapping] - [2011-2014]. 4 records from A new genus and new species of the leafhopper tribe Idiocerini (Hemiptera Cicadellidae: Eurymelinae). 5 records from Two new species of the genus Leptoderes Serville, 1838 (Orthoptera, Tettigoniidae) from China. 255 records from Echinoidea distribution data from: Deep-sea fauna of European seas - an annotated species check-list of benthic invertebrates living deeper than 2000 m in the seas bordering Europe. 13723 records from Harbour seals GPS telemetry in Baie du Mont Saint-Michel. 10295 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 286 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 14 records from New species of Australian microgastrine parasitoid wasps (Hymenoptera: Braconidae: Microgastrinae) documented through the ‘ Bush Blitz’ surveys of national reserves. 487 records from NEON Invertebrate Voucher Collection at Arizona State University. 625 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 49 records from Review of the plant bug tribe Eccritotarsini (Hemiptera: Heteroptera: Miridae) of India and Sri Lanka with description of two new genera and six new species. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 16506 records from Database for alien invasive plants occurrences in Germany. 66 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 205 records from Gandaca butterfly specimens at Museum Zoologi Bogor, Indonesia. 466 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 1335 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1068 records from Trawl-survey data from the Pipeta programme in the Northern Adriatic Sea (Mediterranean) collected in 1988 and 1991. 364 records from Benthic foraminifera abundance of Hole 84-567A, Part 1. 407 records from Strathclyde badger sett surveys 1996-2000. 74 records from UNCW JAX Aerial Survey -Left side- 2017. 80 records from Foraminifera distribution of sediment core SDSE189. 7 records from A new species of Knodus (Characiformes: Characidae) from the Rio Cupari drainage, lower Rio Tapajós basin, Brazil. 3673 records from Spider (NSMK-SP). 155 records from The ceratioid anglerfishes (Lophiiformes: Ceratioidei) of New Zealand. 4348 records from OUPR - Herbário "Professor José Badini". 2017 records from Flore des reliques forestières de la commune de Dangbo. 10 records from Nannofossil abundance of Hole 58-442B. 3 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 17 records from Descriptions of five new species of Homoplectra Ross (Trichoptera, Hydropsychidae) from Japan with reassignment of Homoplectra tohokuensis (Kobayashi). 1 records from Happywhale - Harbor Seal in Southern Ocean. 100 records from Registros de Palma de cera palma (Ceroxylon quindiuense) por medio de fotografías aéreas en el parque Chingaza. 334 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 12399 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase (Entomologica San cristóbal). 21 records from Planktic foraminifera abundance of Hole 18-174. 74 records from Chronicle of Nature - Phenology of Mushrooms of Baikalsky State Nature Biosphere Reserve. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 2693 records from California State University, Long Beach Mammals. 234 records from Royal Saskatchewan Museum - Ichthyology Collection. 25974 records from Long-term Bird Census in Cigu 2004-2017. 14 records from Three new species of Alburnoides from the southern Black Sea basin (Teleostei: Cyprinidae). 2 records from Description of a new genus and four new species of Acaricalini (Acari, Eriophyidae, Phyllocoptinae) from South China. 1 records from Palaearctic species of Charipinae (Hymenoptera, Figitidae): two new species, synthesis and identification key. 372 records from Abundance of living coccolithophores in the northern Arabian Sea (Table 2). 7 records from Contribution to the AIrotropical Ɨchneumoninae (Hymenoptera, Ɨchneumonidae) Irom Gabon and Sierra Leone, with descriptions oI Iive new species and two new subspecies. 2 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 240 records from BARTH-Environnement_2017_12_18. 459 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 1 records from Redescriptions of four Palaeotropical species of the cestode genus Notopentorchis Burt, 1938 (Cyclophyllidea: Paruterinidae). 142 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 493 records from Study of epibenthos and demersal fish in and around the thiocarbamate discharge area of the Belgian Continental Shelf (1977-1981). 109 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1193. 156 records from Total foraminifera counts of multinet M21/2_MSN658. 2 records from Checklist and distribution patterns of apoid wasps (Hymenoptera: Apoidea: Sphecidae and Crabronidae) of Cuba. 17 records from Phytoseiid mites of Slovenia (Acari: Mesostigmata): new records and first description of the male ofAmblyseius microorientalis. 21 records from New State Records Of Kentucky (Usa) Stoneflies (Plecoptera). 30 records from Nannofossil abundance of Hole 9-82. 34 records from Microzooplankton abundance and biomass at station TT043_11-1. 1956 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 2654 records from Patrols activities and fixed transect data collections of the fauna of the W biosphere reserve of Benin of 2017. 37 records from (Table IIIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 1948 records from (Table 4) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-503A from the East Pacific Ocean. 187 records from An annotated type catalogue of the centipedes (Myriapoda: Chilopoda) held in the Zoological Museum Hamburg. 74 records from (Table 5) Planktonic foraminifer species distribution, abundance, and preservation in DSDP Site 92-600. 1377 records from Ghent university - Zoology Museum - Nematod Collection. 79 records from Swedish Malaise Trap Project (SMTP) - Syrphidae. 101 records from BIRDRACE Enger am Spektiv. 32 records from Sciapodinae from the Himalayan region with description of nine new species from Tibet (Diptera: Dolichopodidae). 125 records from Total foraminifera counts from multinet M32/3_MSN956. 254 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 240 records from Tejidos de individuos colectados en el plan de monitoreo de biodiversidad en el bloque platanillo de la empresa Amerisur y en los bloques Rumiyaco, Venados y Burdyne de la empresa Gran Tierra, Putumayo. 981 records from Monitoreo de la ocupación del Oso Andino (Tremarctos ornatus) en el Parque Nacional Natural Chingaza. 5069 records from Données mammifères Midi-Pyrénées enregistrées dans BazNat - Lot 2. 92 records from Nottekanal, Klasse 7 - 10. 414 records from Percentages of planktonic foraminifera species in sediment core V30-40. 29 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 810 records from Environmental long read amplicons of soil fungi across Podzol soil profile. 1 records from A new endemic insular Bent-toed Gecko (Squamata: Gekkonidae: Cyrtodctylus) from Quang Nam Province, Central Vietnam. 2 records from A revision of the Australian species of the genus Melobasis Laporte & Gory 1837 (Coleoptera: Buprestidae), Part 2 (Revision of the nervosa species group). 4733 records from Inventaire des Mollusques Sphaeriidae de France. 16885 records from données aranéologiques de CORNIC Jean-François. 742 records from Programme ACT : Répartition Alouette des champs 2000 - 2004 Coordonnées GPS Lambert 93. 8 records from Four new and three newly recorded species of Diduga Moore, [1887] (Lepidoptera Erebidae, Arctiinae) from China. 54 records from Annotated checklist of the Dermaptera (Insecta) of French Guiana. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 3 records from Systematics and convergent evolution in three Australian genera of Pepsinae spider wasps (Hymenoptera: Pompilidae). 3687 records from Clare Biological Records Centre Dataset 2004-2007. 2424 records from (Figure 2) Quaternary biostratigraphy and planktonic foraminifera of DSDP Hole 72-517. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 2 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 25765 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 1582 records from 2020_biodiversity_information_specimen_cnu. 4 records from A new glass sponge genus (Hexactinellida: Euplectellidae) from abyssal depth of the Yap Trench, northwestern Pacific Ocean. 3919 records from Tasmanian Museum and Art Gallery provider for OZCAM-Arthropoda. 2 records from Two new species of the genus Crangonyx Bate, 1859 (Amphipoda: Crangonyctidae) from the St. Marks River Basin with notes on the “ Crangonyx floridanus complex ”. 1193 records from NEFSC North Atlantic Marine Mammal and Turtle Aerial Abundance Survey 2007. 3 records from The genera Agelosus Sharp, 1889 and Apecholinus Bernhauer, 1933 in Taiwan (Coleoptera: Staphylinidae: Staphylinini: Staphylinina). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 1 records from Filogeografia mitocondrial y nuclear de la Tangara rosada Rhodinocichla rosea (Lesson, 1832): el efecto del aislamiento geográfico y el nicho ecológico en los procesos de divergencia evolutiva.. 20 records from Truchas Mexicanas. 50 records from Flora und Fauna im Brexbachtal. 13639 records from Senckenberg - CeDAMar Resource. 1 records from Endogean and Cavernicolous Coleoptera of the Balkans. XXIII. A new species of Paramaurops J. Müller (Coleoptera: Staphylinidae: Pselaphinae) from Greece. 51 records from Marine metagenome ICM_VAG. 2 records from Two new species of treefrog (Pelodrydidae: Litoria) from southern New Guinea elucidated by DNA barcoding. 14619 records from Ontario Breeding Bird Atlas 1981-1985. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 3889 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 1 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 391 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 244 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 564 records from Biological Collection, National Institute of Oceanography, Goa, India. 72142 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 133 records from Pollen profile II/B at Krumbach, Germany. 1579 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 1000 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 22136 records from Weevil and Bark Beetle records via iRecord. 93 records from A revision of the genus Mesoconius Enderlein (Diptera, Micropezidae, Taeniapterinae). 51 records from Chronicle of Nature - Phenology of Reptiles of Pechoro-Ilych State Nature Reserve. 16 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 31 records from Nationalpark Harz Schul-AG Braunlage. 7 records from A new apterous rove beetle genus (Coleoptera: Staphylinidae) from the Northern Andes with an assessment of its phylogenetic position. 677 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 90 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 38 records from Was lebt in der Brutzwiese?. 2 records from Description of the male and larva of Schizomyia tuiuiu Urso- Guimarães & Amorim (Diptera, Cecidomyiidae), new records and a key to Neotropical species of Schizomyia Kieffer. 3458 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 224 records from The Avian Collection of the Tana River Basin at the National Museums of Kenya's Ornithology Section.. 19 records from The genus Passaloecus Shuckard (Hymenoptera: Crabronidae) from China with four new species and two new records. 5621 records from Plan d'Aménagement participative de la Forêt Classée d'Alédjo (Togo). 1648 records from (Table 3) Dead benthic foraminifera in surface sediments from the eastern South Atlantic Polar Front region. 24 records from Two new trans-Andean species of Imparfinis Eigenmann & Norris, 1900 (Siluriformes: Heptapteridae) from Colombia. 2 records from A New Iranian Species Of The Subgenus Labidostoma (Prostigmata: Labidostomatidae), With New Biogeographic Data On The Integrum Species Group. 3 records from A review of the Barsine perpallida-B. yuennanensis species-group, with descriptions of six new species (Lepidoptera: Erebidae: Arctiinae). 2011 records from UNCW Right Whale Aerial Surveys 2008. 11 records from Benthic macrofauna abundance of sediment core 13078-013. 1084 records from Planktic foraminifera counts of sediment core RC14-35. 263 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 2 records from A new species of Aoruroides Travassos & Kloss, 1958 (Nematoda: Oxyuridomorpha Thelastomatidae) parasite of the wood-burrowing cockroach Panesthia angustipennis spadica (Shiraki, 1906) (Blattodea: Blaberidae: Panesthiinae) from Japan with comments on the validity of the genus Aoruroides. 3 records from Nouveautés dans le genre Lomariopsis Fée (Pteridophyta, Lomariopsidaceae) à Madagascar: trois espèces nouvelles et une espèce africaine nouvellement signalée. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 29 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 1296 records from Avifauna de los Parques Ecológicos Distritales de Montaña del Distrito Capital. 3 records from A new species of Aphantolana Moore & Brusca, 2003 (Crustacea: Isopoda Cirolanidae) from the Andaman Islands, northern Indian Ocean. 1569 records from Pollen record of sediment core Bokanjacko Blato 1. 21 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 1 records from A new species of Leiochrides Augener, 1914 (Annelida: Capitellidae) from the Beibu Gulf, South China Sea. 21 records from Cape Verde (Cabo Verde) 2005: Loggerhead Turtles (aggregated per 1-degree cell). 168 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 661 records from Données espèces Expertise IQE 311. 60 records from Fish species observations from a monitoring survey of two Lake Victoria affluent rivers (Rivers Kagera and Sio). 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 4 records from Amphilochidae *. 82 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 1 records from Tyrannosaurus rex from the McRae Formation (Lancian, Upper Cretaceous), Elephant Butte Reservoir, Sierra County, New Mexico. 15130 records from MMS Surveys, SCB 1995-1997. 15 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 67612 records from India Biodiversity Portal publication grade dataset. 138 records from Range table from benthic foraminifers in ODP Hole 198-1209C. 27 records from (Table 2) Distribution of early late Eocene fossil content in ODP Hole 115-714A. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 574 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3083 records from Butterflies of Singapore and Peninsular Malaysia (Lycaenidae). 87 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 4658 records from All herbarium specimens of grasses held at TAN herbarium. 749850 records from Oiseaux de France métropolitaine en hiver 1977-1981. 1 records from A taxonomic note of Pterocephalus (Caprifoliaceae) from N Iran. 1 records from Acromyrmex fowleri: a new inquiline social parasite species of leaf-cutting ants from South America, with a discussion of social parasite biogeography in the Neotropical region. 548 records from Pollen counts of sediment core GeoB9503-5. 61 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 1515 records from Mammals in the collection of Zoological Museum of NSNHM (the National Science and Natural History Museum at the National Academy of Sciences of Ukraine, Kyiv): Erinaceidae, Talpidae, Soricidae, Myoxidae, Sminthidae. 14 records from Nemertini - SMF. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 1 records from A new species of Microhyla Tschudi, 1838 (Anura: Microhylidae) from West Coast of India: an integrative taxonomic approach. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 266 records from Chronicle of Nature - Phenology of Insects of Volzhsko-Kamsky National Nature Biosphere Rezerve. 56 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 66620 records from Benthos monitoring in the intertidal mudflats of Pertuis-Charentais (Bay of Biscay) from 2004 on. 409 records from Records of fish species in coastal lagoons from Municipality of Arta, for the period 1999-2011. 10774 records from Some Angiosperm Data of the Forest Herbarium Ibadan (FHI) Nigeria. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 24 records from Abundance of coccosphere-units of sediment core GIK23071-3. 3 records from A new species of Cyrtodactylus Gray (Squamata; Gekkonidae) from the Thai Highlands with a discussion on the evolution of habitat preference. 74 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 30-63 µm fraction. 525 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 183 records from Nannofossil abundance of Hole 67-496. 852 records from Observatoire des Mammifères marins de l'Archipel Guadeloupéen. Suivi Dauphins Les Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 221 records from Acoustic detections from R/V Song of the Whale during the spring 2019 MAPS survey (NMFS permit 14809). 1863 records from Coral Reef Evaluation and Monitoring Project Dry Tortugas 2008. 841 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 2 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 2 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 90 records from NMML Harbor Porpoise Aerial Survey, Kodiak Island, Replicate 3, 1992. 3 records from Taxonomic noteson thegenusPseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae Eumeninae) from Vietnam with key to all known species in the Oriental region. 76 records from SFSU - Vascular Plants of the Harry D. Thiers Herbarium at San Francisco State University. 361 records from Colección de Crustáceos del Instituto de Ciencias Naturales (ICN-MHN-Cr). 2045 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 16 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 235 records from Pollen and spore abundance of Hole 42-381. 324893 records from Estonian Nature Observations Database. 14 records from New and little known species of Halolaelaps (Acari: Mesostigmata: Halolaelapidae) from Ukraine. 9 records from On the Neotropical spider genus Tullgrenella Mello-Leitão, 1941: two new species complementary descriptions and new records (Araneae: Salticidae). 14 records from New species of deep-water Calcigorgia gorgonians (Anthozoa: Octocorallia) from the Sea of Okhotsk, with a re-diagnosis and a taxonomic review of the genus. 23 records from 2017 Onwards Rare Invertebrates in the Cairngorms Northern Silver Stiletto Fly Survey Data. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 5 records from Genome sequencing reveals extraordinary cephalic horns in the Madagascan dung beetle genus Helictopleurus (Coleoptera, Scarabaeinae): insight from a revision of fungicola species group. 38375 records from Botanical Museum, Copenhagen, Mycology Herbarium. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 7 records from Description of a new species of Moenkhausia (Characiformes: Characidae) from the upper Paraguay basin, Central Brazil, with comments on its phylogenetic relationships. 11686 records from NCSM Mammalogy Collection. 798 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 16 records from Nannofossil abundance of Hole 52-418. 24 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 91 records from Heard Island Shag Phalacrocorax nivalis census, Heard Island 1992. 84 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 11 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 235 records from Chronicle of Nature - Phenology of Insects of Kaniv Nature Reserve. 770 records from Nivå Bay species list, Zealand, Denmark. 3317 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 171 records from Fungal Bioblitz in Białowieża Primeval Forest at 18th Congress of European Mycologists. 7 records from Swedish Malaise Trap Project (SMTP) - Mymar. 797 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 452 records from Nannofossil abundance of Hole 64-476. 45 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 2375 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 7255 records from Colección general del plantas vasculares del Herbario JBB. 91645 records from Colección de Entomología del Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-E). 2 records from New Vietnamese Species Of The Genus Flavoperla Chu (Plecoptera: Perlidae). 160 records from Seabird sightings in Ghana and Ivorycoast. 211863 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2018. 7 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 1441 records from Cowan Tetrapod Collection - Herpetology. 147 records from Total foraminifera counts from multinet M31/3_MSN898. 4 records from Taxonomic update of the Neotropical genus Cryptocladocera Bezzi, 1923 (Diptera: Tachinidae), with remarks on tachinids with fissicorn antennae. 2 records from The discovery and description of a new species of Bent-toed Gecko of the Cyrtodactylus pulchellus complex (Squamata: Gekkonidae) from the Langkawi Archipelago, Kedah, Peninsular Malaysia. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 186 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Sinoperlodes, a new genus of subfamily Perlodinae (Plecoptera, Perlodidae) from coastal southeastern China. 17 records from New species of Duplominona Karling, 1966 (Platyhelminthes, Proseriata) from the Pacific coast of Panama. 36363 records from Royal Belgian Institute of Natural Sciences Mammal collection. 3 records from Eleven new species and a new country record of Pselaphodes (Coleoptera: Staphylinidae: Pselaphinae) from China, with a revised checklist of world species. 29 records from Hemmerder Schelk (Unna). 84 records from Shellfish (MNHM-MS). 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 30998 records from Elephant Seal Sightings, Macquarie Island. 411 records from A monograph of the genus Maladera Mulsant & Rey, 1871 of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini). 2 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 53 records from CHAS Botany Collection (Arctos). 203 records from Total foraminifera counts of multinet M21/1_MSN604. 237 records from Avifauna asociada a humedales urbanos del municipio de Quibdó - Chocó, 2019. 4 records from Leuctra Pinhoti, A New Species Of Stonefly (Plecoptera: Leuctridae) From Alabama, U. S. A.. 3 records from Description of a new species of Music frogs (Anura, Ranidae, Nidirana) from Mt Dayao, southern China. 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 465 records from Hyperbenthos community in the salt marsh of Saeftinghe in 1990 and 1991. 16 records from jamaica_invasive_alien_species. 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 15 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 2 records from Bryoerythrophyllum subcaespitosum (Pottiaceae), a new combination for a neglected species from South America. 19 records from Hiding in plain sight: rediscovery and review of Parygrus Erichson, 1847, with description of five new species from the Neotropics (Coleoptera: Byrrhoidea Dryopidae). 3 records from A new species of the spider genus Phlogiellus (Araneae, Theraphosidae) from Hainan, China. 1 records from A new tardigrade species of the genus Neostygarctus Grimaldi de Zio et al., 1982 (Tardigrada, Arthrotardigrada) from the Great Meteor Seamount, Northeast Atlantic. 272720 records from Parc_National_de_Port_Cros_2017_12_18. 4 records from Distribution of Quinqueloculina sp. in sediment core 13077-089. 39640 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 15 records from Morphology and molecular data reveal the presence of two new species under Rhamdia quelen (Quoy & Gaimard, 1824) (Siluriformes: Heptapteridae) species complex. 831 records from MAG Herbarium: collections of vascular plants. 5 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 1 records from Pentatomiana beckerae gen. nov. and sp. nov., a new Neotropical Pentatomini (Hemiptera, Heteroptera, Pentatomidae). 25 records from Happywhale - Crabeater Seal in Southern Ocean. 401 records from Planktic foraminifera distribution of sediment core SU81-07. 926 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 4 records from Minooa Yamanaka, 1996, a genus newly recorded to China with description of a new species (Lepidoptera, Pyralidae, Pyralinae). 3 records from A new group of species within the bee genus Ruizantheda, with a revised key to the males of the genus (Hymenoptera: Halictidae: Caenohalictini). 85 records from Ecología de comunidades microbianas en las aguas subterráneas de Cuatrociénegas, Coahuila. 2 records from A new black fly species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Sulawesi, Indonesia. 51 records from A review of the genus Hexachaetoniella Paschoal in Australia (Acarina: Cryptostigmata: Pedrocortesellidae). 31 records from The genus Coenosia Meigen in Iran, with a key to species and description of a new species (Diptera: Muscidae). 20887 records from Brachycera (Diptera) records from Britain and Ireland to 1990. 438 records from Vermont Freshwater Mussel Atlas 1995. 3893 records from Colección Carcinológica de Yucatán. 22 records from Satellite Tracking of Hawksbill Turtles in Melaka, Malaysia (aggregated per 1-degree cell). 466 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 15 records from Bulletin de la Société Linnéenne de Bordeaux, Tome 145 (N.S) n° 38 (1), 2010 - Données faune. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 12 records from Benthic foraminifera abundance of Hole 96-620. 5407 records from FrogWatch SA. 99 records from Nanoplankton abundance at station GeoB2006-4. 75 records from Données naturalistes de Françoise SERRE-COLLET. 2 records from Happywhale - Galpagos sea lion in South Pacific Ocean. 374 records from (App 5) Relative contents of benthic foraminifera species in Holocene sediments from Core BP01-62/04. 2 records from Another unusual new gorgonian (Anthozoa: Octocorallia: Plexauridae) from the Aleutian Islands of Alaska. 319 records from Données naturalistes de Monsieur LEFEBVRE François. 30 records from Chronicle of Nature - Phenology of Reptiles of State Nature Reserve Malaya Sosva. 2 records from Bopopia, a new monotypic genus of Gesneriaceae (Gesnerioideae, Coronanthereae) from New Caledonia. 78 records from Spain-Baleric Is. 2015 Loggerhead Turtles (aggregated per 1-degree cell). 1351 records from Range table from planktonic foraminifers in ODP Hole 144-872C. 2 records from Redescription of Admete sadko Gorbunov, 1946 (Gastropoda: Cancellariidae). 2 records from A new species of Traverella Edmunds, 1948 (Ephemeroptera: Leptophlebiidae) from Brazil. 1814 records from UKSBA Cyprus - Habitat Samples, 2019. 130434 records from Herbarium of Taiwan Forestry Research Institute. 90 records from Swedish Malaise Trap Project (SMTP) - Pallopteridae. 11 records from ALP-PAGES_2017_12_18. 23 records from Ackerrain Plönhagen. 6936 records from Colección Herpetológica (Anfibios) del Museo de Historia Natural de la Universidad Industrial de Santander. 1 records from Great Sippewissett Marsh Plot nirS Targeted Locus. 1004 records from Données odonates. 242 records from Malawi-Histeridae-Biodiversity-Data. 1994 records from Actualización de la base de datos de la Colección Regional Durango (Tejido). 426 records from Planktic foraminifera abundance of Hole 7-64. 25 records from New species of subterranean and endogean terrestrial isopods (Crustacea, Oniscidea) from Tuscany (central Italy). 1 records from Museu Paraense Emílio Goeldi - Acanthocephala Collection. 1 records from A new species of Cofana associated with grasses from India (Hemiptera: Cicadellidae: Cicadellinae). 3 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB5. 22 records from Bachabschnitt der Nette (Osnabrück). 17244 records from Registros biológicos asociados al monitoreo de la diversidad de escarabajos en paisajes ganaderos de bosque 2013 - 2017. 1 records from A new freshwater chrysophyte, Chrysomorula cohaerens gen. et sp. nov. (Chrysophyceae, Chrysocapsaceae) from North America. 115211 records from Santa Barbara Museum of Natural History Entomology Collection. 358 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 2 records from Teretamon spelaeum, a new species of freshwater crab (Crustacea: Decapoda: Potamidae) from a limestone cave in Meghalaya, India. 1567 records from Occurrence of wild and cultivated yams observed in West Africa and Madagascar from 1996 to 2015. 491 records from Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 3 records from A supplemental description of the genus Lista Walker from China (Lepidoptera: Pyralidae), with two new and a newly record species. 46736 records from Mangroves of the Northern Territory, 1:100,000, Australia (1996). 165 records from Mortensen Th. And Steuer Ad. 1937. The fishery grounds near Alexandria. XIII Echinoderma. Notes and Memoirs No 21. Hydrobiology and Fisheries Directorate, Egypt. 2 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 54858 records from The fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Tretogonia Melichar (Hemiptera: Cicadellidae: Proconiini): two new species from South Brazil and a redescription of T. dentalis Emmrich, 1988. 400 records from (Table 1) Abundance of Globigerinoides sacculifer and Globigerinoides ruber and oxygen and carbon stable isotopes of different planktonic foraminifers at DSDP Hole 78-541. 254 records from Range table from planktonic foraminifers in ODP Hole 155-930C. 114 records from BIRDRACE Di-Bi-Di-Birder. 2 records from A new species of Ancistrus Kner, 1854 (Siluriformes: Loricariidae) from rio Madeira basin, Amazonas State, Brazil. 6 records from A new species of the genus Liljeborgia Spence Bate, 1862 (Crustacea: Amphipoda: Liljeborgiidae) associated with the burrows of the spoon worm Urechis unicinctus in the Sea of Japan. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 19665 records from EDP Baixo
Keywords: GBIF; biodiversity; species occurrences